Steel material and crankshaft made of said steel material

JP7635371B2Active Publication Date: 2025-02-25NIPPON STEEL CORPORATION +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023523820
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-26
Publication Date
2025-02-25
Estimated Expiration
2041-05-26

AI Technical Summary

Benefits of technology

【0014】 本開示による鋼材は、被削性に優れ、窒化処理を実施してクランクシャフトとした場合に優れた曲げ疲労強度、優れた耐摩耗性、及び、優れた曲げ矯正性を有する。本開示によるクランクシャフトは、優れた曲げ疲労強度、優れた耐摩耗性、及び、優れた曲げ矯正性を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635371000008
    Figure 0007635371000008
  • Figure 0007635371000009
    Figure 0007635371000009
  • Figure 0007635371000010
    Figure 0007635371000010
Patent Text Reader

Abstract

The present invention provides a steel material which has excellent machinability, bending fatigue strength, wear resistance and bending straightening properties. This steel material contains, in mass%, 0.25% to 0.35% of C, 0.05% to 0.35% of Si, 0.85% to 1.20% of Mn, 0.080% or less of P, 0.030% to 0.100% of S, 0.10% or less of Cr, 0.050% or less of Ti, 0.050% or less of Al, 0.005% to 0.024% of N and 0.0100% or less of O, with the balance being made up of Fe and impurities; and with respect to this steel material, Fn1 set forth in the description is 1.00 to 2.05, and Fn2 set forth in the description is 0.42 to 0.60. The surface number density of MnS simple inclusions and MnS composite inclusions, each having a circle-equivalent diameter of 5.0 μm or more, is 20 per mm2 or more; the ratio of the total number of MnS simple inclusions and MnS composite inclusions relative to the total number of inclusions is 70% or more; and the ratio of the number of MnS composite inclusions relative to the total number of oxides is 30% or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel material and a crankshaft, and more particularly to a steel material that is a raw material for a crankshaft, and a crankshaft manufactured by subjecting the steel material to a nitriding treatment. [Background technology]

[0002] Crankshafts are used in transportation equipment such as automobiles, trucks, and construction machines. Crankshafts are required to have excellent bending fatigue strength. Furthermore, idling stop technology, which repeatedly starts and stops the engine, has become widespread recently in order to reduce environmental impact. If the frequency of repeatedly starting and stopping the engine increases, the crankshaft operates more frequently before an oil film (oil film made of engine oil) is sufficiently formed on the sliding parts such as the pin and journal parts of the crankshaft. Furthermore, recently, the viscosity of engine oil has been reduced in order to improve fuel efficiency. Therefore, the thickness of the oil film that protects the sliding parts of the crankshaft tends to decrease. Therefore, crankshafts are required to have not only excellent bending fatigue strength but also excellent wear resistance.

[0003] Furthermore, with the demand for improved fuel efficiency, weight reduction of transport aircraft parts is being promoted. As a result, crankshafts with complex shapes that are difficult to machine have appeared, which were not applicable in the past. Therefore, the steel material for crankshafts must have excellent machinability.

[0004] Among the bending fatigue strength, wear resistance, and machinability described above, nitriding is known as a technique for increasing the bending fatigue strength and wear resistance of crankshafts. Here, the nitriding in this specification also includes soft nitriding. The nitriding is a heat treatment technique in which nitrogen (or nitrogen and carbon) is diffused and penetrated into the surface layer of a steel material at a temperature below the A1 transformation point. A nitride layer consisting of a compound layer and a diffusion layer is formed on the surface layer of a crankshaft that has been subjected to nitriding. The compound layer is formed on the outermost surface layer of the crankshaft, is mainly composed of nitrides represented by Fe3N, and has a depth of about several tens of μm to 30 μm. The diffusion layer is formed inside the compound layer, is a region hardened by nitrogen diffused inside the steel material, and has a depth of about several hundreds of μm. The nitriding is characterized in that the distortion generated after the heat treatment is small compared to other surface hardening heat treatments such as induction hardening and carburizing.

[0005] However, even nitriding cannot completely eliminate distortion after heat treatment. High straightness is especially required for crankshafts. For this reason, a bending straightening process is usually performed on the crankshaft after nitriding to improve the straightness of the crankshaft. If cracks occur in the crankshaft during bending straightening, the bending fatigue strength will decrease significantly. Therefore, steel materials for nitriding are required to have excellent bending straightening properties, that is, properties that suppress the occurrence of cracks during the bending straightening process.

[0006] Techniques for improving the bending fatigue strength and wear resistance of nitrided parts, such as crankshafts, are disclosed in WO 2016 / 182013 (Patent Document 1) and JP 2013-7077 A (Patent Document 2).

[0007] The nitrided parts disclosed in Patent Document 1 have a compound layer mainly made of gamma prime (γ') phase (Fe4N) and a thick compound layer mainly made of γ' phase by controlling the nitriding potential in a nitriding furnace. Patent Document 1 states that by making the compound layer mainly made of γ' phase, it is possible to increase the wear resistance of the nitrided parts while maintaining their fatigue strength.

[0008] In Patent Document 2, a fluoridation pretreatment is performed, followed by a nitriding treatment. As a result, a wear-resistant layer (first diffusion layer) in which carbon and nitrogen are concentrated is formed on the surface of the steel material, and a carbon-based diffusion layer (second diffusion layer) with a lower nitrogen concentration is formed inside the steel material than the first diffusion layer. Patent Document 2 describes that the formation of a nitrided layer having such a configuration results in excellent fatigue strength and wear resistance. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2016 / 182013 [Patent Document 2] JP 2013-7077 A Summary of the Invention [Problem to be solved by the invention]

[0010] The fatigue strength and wear resistance of the crankshaft may be increased by techniques other than those disclosed in Patent Documents 1 and 2. However, Patent Documents 1 and 2 do not consider the machinability of the steel material from which the crankshaft is made or the straightening ability of the crankshaft.

[0011] An object of the present disclosure is to provide a steel material that can be used as a raw material for crankshafts, which has excellent machinability and, when subjected to nitriding treatment to form a crankshaft, has excellent bending fatigue strength, excellent wear resistance, and excellent bending straightening properties, and to provide a crankshaft made from that steel material. [Means for solving the problem]

[0012] The steel material according to the present disclosure is In mass%, C: 0.25%~0.35%, Si: 0.05 to 0.35%, Mn: 0.85-1.20%, P: 0.080% or less, S: 0.030~0.100%, Cr: 0.10% or less, Ti: 0.050% or less, Al: 0.050% or less, N: 0.005 to 0.024%, and O: 0.0100% or less, the balance being Fe and impurities, Fn1 defined by formula (1) is 1.00 to 2.05, Fn2 defined by formula (2) is 0.42 to 0.60, Among the inclusions in the steel material, An inclusion whose total Mn content and S content is 80.0% or more by mass% is defined as a single MnS inclusion. An inclusion whose total Mn content and S content is less than 15.0 to 80.0% by mass is defined as an MnS composite inclusion. An inclusion having an Al content, Ca content and O content of 80.0% or more by mass and an Mn content and S content of less than 15.0% by mass is defined as a single oxide. When the inclusions having an Al content, a Ca content, and an O content of 15.0 to less than 80.0% by mass and an Mn content and an S content of 15.0 to less than 80.0% by mass are defined as MnS composite oxides, In the steel material, The total surface density of the MnS single inclusions having an equivalent circle diameter of 5.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 5.0 μm or more is 20 pieces / mm 2 That's all. a ratio of the total number of the MnS single inclusions having an equivalent circle diameter of 1.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 1.0 μm or more to the total number of inclusions having an equivalent circle diameter of 1.0 μm or more is 70% or more; The ratio of the number of the MnS composite oxides having an equivalent circle diameter of 1.0 μm or more to the total number of the single oxides having an equivalent circle diameter of 1.0 μm or more and the MnS composite oxides having an equivalent circle diameter of 1.0 μm or more is 30% or more. Fn1 = Mn + 7.24 Cr + 6.53 Al (1) Fn2=C+0.10Si+0.19Mn+0.23Cr-0.34S...(2) Here, the content of each element in formula (1) and formula (2) is substituted in mass % for each element symbol corresponding to the element.

[0013] The crankshaft according to the present disclosure comprises: A pin portion and The journal section and an arm portion disposed between the pin portion and the journal portion, At least the pin portion and the journal portion are A nitride layer formed on the surface; A core portion located inside the nitride layer, The core portion comprises, in mass%, C: 0.25%~0.35%, Si: 0.05 to 0.35%, Mn: 0.85-1.20%, P: 0.080% or less, S: 0.030~0.100%, Cr: 0.10% or less, Ti: 0.050% or less, Al: 0.050% or less, N: 0.005 to 0.024%, and O: 0.0100% or less, the balance being Fe and impurities, Fn1 defined by formula (1) is 1.00 to 2.05, Fn2 defined by formula (2) is 0.42 to 0.60, Among the inclusions in the core portion, An inclusion whose total Mn content and S content is 80.0% or more by mass% is defined as a single MnS inclusion. An inclusion whose total Mn content and S content is less than 15.0 to 80.0% by mass is defined as an MnS composite inclusion. An inclusion having an Al content, Ca content and O content of 80.0% or more by mass and an Mn content and S content of less than 15.0% by mass is defined as a single oxide. When the inclusions having an Al content, a Ca content, and an O content of 15.0 to less than 80.0% by mass and an Mn content and an S content of 15.0 to less than 80.0% by mass are defined as MnS composite oxides, In the core portion, The total surface density of the MnS single inclusions having an equivalent circle diameter of 5.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 5.0 μm or more is 20 pieces / mm 2 That's all. a ratio of the total number of the MnS single inclusions having an equivalent circle diameter of 1.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 1.0 μm or more to the total number of inclusions having an equivalent circle diameter of 1.0 μm or more is 70% or more; The ratio of the number of the MnS composite oxides having an equivalent circle diameter of 1.0 μm or more to the total number of the single oxides having an equivalent circle diameter of 1.0 μm or more and the MnS composite oxides having an equivalent circle diameter of 1.0 μm or more is 30% or more. Fn1 = Mn + 7.24 Cr + 6.53 Al (1) Fn2=C+0.10Si+0.19Mn+0.23Cr-0.34S...(2) Here, the content of each element in formula (1) and formula (2) is substituted in mass % for each element symbol corresponding to the element. Effect of the Invention

[0014] The steel material according to the present disclosure has excellent machinability, and when nitrided into a crankshaft, has excellent bending fatigue strength, excellent wear resistance, and excellent straightening ability. The crankshaft according to the present disclosure has excellent bending fatigue strength, excellent wear resistance, and excellent straightening ability. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic diagram for explaining the positions at which samples for identifying inclusions are taken from the steel material that is the raw material for the crankshaft. [Diagram 2] FIG. 2 is a diagram showing an example of a main part of the crankshaft of the present embodiment. [Diagram 3]FIG. 3 is a cross-sectional view of the vicinity of the surface layer of a pin portion or a journal portion of the crankshaft in FIG. [Figure 4] FIG. 4 is a side view of a bending fatigue test piece for use in an Ono-type rotating bending fatigue test according to an embodiment. [Diagram 5] FIG. 5 is a front view, a side view, and a plan view of a bending test piece for a four-point bending test of the embodiment. [Figure 6] FIG. 6 is a perspective view showing a block-on-ring wear tester in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present inventors have investigated a steel material that can be used as a raw material for crankshafts, which has excellent machinability during the manufacturing process of the crankshaft, and which, when subjected to nitriding treatment to form a crankshaft, exhibits excellent bending fatigue strength, excellent wear resistance, and excellent bending straightenability.

[0017] First, the inventors of the present invention investigated the chemical composition of a steel material that can improve the above-mentioned machinability and can improve the bending fatigue strength, wear resistance, and bending straightening property when used in a crankshaft. As a result, the steel material has the following composition by mass: C: 0.25% to 0.35%, Si: 0.05 to 0.35%, Mn: 0.85 to 1.20%, P: 0.080% or less, S: 0.030 to 0.100%, Cr: 0.10% or less, Ti: 0.050% or less, Al: 0.050% or less, N: 0.005 to 0.024%, O: 0.0100% or less, Cu: 0 to 0.20%, Ni: 0 to 0.20%, Mo: 0 to 0.10%, Nb: 0 to 0.20%, and Nb: 0 to 0.20%. It was thought that if a steel material had a chemical composition of 0.050%, Ca: 0-0.0100%, Bi: 0-0.30%, Te: 0-0.0100%, Zr: 0-0.0100%, Pb: 0-0.09%, and the balance being Fe and impurities, it would be possible to improve machinability, and further, when nitrided to make a crankshaft, it would be possible to improve bending fatigue strength, wear resistance, and bending straightenability. Therefore, based on the above-mentioned chemical composition, an investigation was conducted on the machinability, bending fatigue strength, wear resistance, and bending straightenability.

[0018] The bending fatigue strength after nitriding is positively correlated with the hardness of the nitride layer formed on the surface layer of the steel material after nitriding and the hardness of the core portion deeper than the nitride layer. On the other hand, the bending straightening property after nitriding is negatively correlated with the hardness of the nitride layer of the steel material after nitriding. Furthermore, the machinability is negatively correlated with the hardness of the steel material before nitriding (i.e., in the case of a steel material after nitriding, the core portion not affected by the nitriding). Therefore, in order to improve the bending fatigue strength, wear resistance, and bending straightening property after nitriding and to improve the machinability of the steel material during the manufacturing process of the crankshaft, it is necessary to control the hardness of the nitride layer of the steel material after nitriding and the hardness of the core portion of the steel material after nitriding within a certain range.

[0019] The hardness of the nitride layer of a steel material after nitriding is determined by the hardness of the steel material before nitriding and the increase in hardness of the steel material surface layer due to nitriding. Here, "the increase in hardness of the steel material surface layer due to nitriding" means the difference between the hardness of the nitride layer formed by nitriding and the hardness of the steel material before nitriding. In other words, the higher the hardness of the steel material before nitriding (i.e., the core of the steel material after nitriding) and the larger the increase in hardness of the steel material surface layer due to nitriding, the higher the hardness of the nitride layer of the steel material after nitriding.

[0020] Here, the inventors considered that in steel having the above-mentioned chemical composition, the hardness of the steel before nitriding (i.e., the core after nitriding) depends on the contents of C, Si, Mn, and Cr, which are elements that increase the hardness of the steel by solid solution strengthening, and the content of S, which is an element that embrittles the steel. Furthermore, the inventors considered that the increase in hardness of the steel surface layer due to nitriding depends on the contents of Mn, Cr, and Al, which are elements that have a high affinity for nitrogen.

[0021] Therefore, the present inventors have investigated the relationship between the contents of elements (Mn, Cr, Al) that increase the hardness of the surface layer of the steel after nitriding, and the contents of elements (C, Si, Mn, Cr, and S) that affect the core hardness after nitriding, and the machinability, bending fatigue strength, wear resistance, and bending straightenability of the steel, in which the contents of each element in the chemical composition are within the above-mentioned ranges. As a result, the present inventors have obtained the following findings.

[0022] Fn1 is defined by equation (1), and Fn2 is defined by equation (2). Fn1 = Mn + 7.24 Cr + 6.53 Al (1) Fn2=C+0.10Si+0.19Mn+0.23Cr-0.34S...(2) Here, the content of each element in formula (1) and formula (2) is substituted in mass % for each element symbol corresponding to the element.

[0023] Fn1 is an index of the increase in hardness of the surface layer of a steel material due to nitriding in a steel material in which the content of each element in the chemical composition is within the above-mentioned range. In other words, Fn1 is related to the bending fatigue strength and bending straightening property of the steel material after nitriding, on the premise that the content of each element in the chemical composition of the steel material is within the above-mentioned range. If Fn1 is less than 1.00, even if the content of each element in the chemical composition is within the range of this embodiment and Fn2 is within the range of this embodiment, sufficient bending fatigue strength cannot be obtained in the crankshaft, which is the steel material after nitriding. On the other hand, if Fn1 exceeds 2.05, even if the content of each element in the chemical composition is within the range of this embodiment and Fn2 is within the range of this embodiment, the bending straightening property of the steel material after nitriding is reduced. If Fn1 is 1.00 to 2.05, on the premise that the content of each element in the chemical composition is within the range of this embodiment and Fn2 is within the range of this embodiment, sufficient bending fatigue strength and sufficient bending straightening property can be obtained in the crankshaft.

[0024] Fn2 is an index of hardness of a steel material before nitriding (i.e., the core of the steel material after nitriding) in a steel material in which the content of each element in the chemical composition is within the above-mentioned range. Fn2 is related to the machinability of the steel material and the bending fatigue strength of the steel material after nitriding, on the premise that the chemical composition of the steel material is within the above-mentioned range. If Fn2 is less than 0.42, even if the content of each element in the chemical composition is within the range of this embodiment and Fn1 is within the range of this embodiment, sufficient bending fatigue strength cannot be obtained in the crankshaft, which is the steel material after nitriding. On the other hand, if Fn2 exceeds 0.60, even if the content of each element in the chemical composition is within the range of this embodiment and Fn1 is within the range of this embodiment, sufficient machinability cannot be obtained in the steel material. If Fn2 is 0.42 to 0.60, on the premise that the elements in the chemical composition are within the range of this embodiment and Fn1 is within the range of this embodiment, sufficient machinability can be obtained in the steel material and sufficient bending fatigue strength can be obtained in the crankshaft.

[0025] As described above, by setting the chemical composition within an appropriate range, the machinability of the steel material and the bending fatigue strength and bending straightenability of the steel material after nitriding can be improved to a certain degree. Therefore, the present inventors further investigated ways to improve the machinability of the steel material and the wear resistance of the steel material after nitriding by factors other than the chemical composition. Here, the present inventors investigated not only the machinability but also the wear resistance, focusing on inclusions. As a result, the following findings were obtained regarding inclusions that affect machinability and wear resistance. In the following explanation, inclusions are defined as follows.

[0026] (a) When the mass percentage of inclusions is taken as 100%, an inclusion with a total content of Mn and S of 80.0% or more by mass is defined as a "single MnS inclusion". (b) When the mass percent of the inclusions is taken as 100%, inclusions with a total content of Mn and S of 15.0 to less than 80.0 mass percent are defined as "MnS composite inclusions". (c) When the mass percent of the inclusions is 100%, an inclusion whose total content of Al, Ca, and O is 80.0% or more by mass, and whose total content of Mn and S is less than 15.0% by mass, is defined as a "single oxide." (d) When the mass percent of inclusions is 100%, the inclusions having a total Mn and S content of 15.0 to less than 80.0% by mass and a total Al, Ca and O content of 15.0 to less than 80.0% by mass are defined as "MnS composite oxides". Hereinafter, MnS single inclusions and MnS composite inclusions are collectively referred to as “MnS-based inclusions.” As defined above, MnS composite oxides are included in the MnS composite inclusions.

[0027] Machinability is affected not only by the hardness of the steel before nitriding (the core of the steel after nitriding), but also by the inclusions. Specifically, the surface density (number / mm2) of MnS-based inclusions (single MnS inclusions and MnS compound inclusions) present in the steel 2 ) improves machinability. However, if the size of the MnS inclusions is too small, their impact on machinability is small. Specifically, if the MnS inclusions have an equivalent circle diameter of less than 5.0 μm, their impact on the machinability of the steel is extremely small. Therefore, in order to improve the machinability of the steel, it is effective to increase the surface density of MnS inclusions with an equivalent circle diameter of 5.0 μm or more. The equivalent circle diameter refers to the diameter of a circle when the area of ​​each inclusion is converted into a circle having the same area.

[0028] Furthermore, the inclusions also affect the wear resistance of the steel material after nitriding. A compound layer is formed on the outermost surface of the nitrided layer formed on the surface of the steel material after nitriding. In a crankshaft manufactured by carrying out nitriding, cracks occur and grow in this compound layer, causing the compound layer to peel off, and wear progresses. The compound layer is formed when a part that was originally steel material is transformed by the nitriding treatment to contain a large amount of nitrogen. If inclusions are present in the surface layer of the steel material before nitriding, and the surface layer is transformed into a compound layer by the nitriding treatment, the compound layer will contain the inclusions.

[0029] The present inventors considered that the occurrence of cracks in the compound layer may be caused by inclusions in the compound layer. Therefore, the present inventors focused on the type of inclusions and investigated the relationship with the occurrence of cracks in the compound layer. As a result, it was found that most of the cracks in the compound layer that cause wear originate from hard oxides. In addition, it was found that soft MnS-based inclusions are unlikely to be the starting point of cracks in the compound layer, and further, MnS composite oxides, which are composite inclusions of MnS-based inclusions and single oxides, are also unlikely to be the starting point of cracks in the compound layer. Therefore, the present inventors considered that in order to increase the wear resistance of a crankshaft manufactured by nitriding, it is effective to reduce the amount of single oxides as much as possible or to make the single oxides into composite inclusions with MnS (MnS composite oxides).

[0030] However, since oxides in molten steel become nuclei for the formation of MnS-based inclusions, a certain amount of oxygen in molten steel is required for the formation of MnS-based inclusions. Therefore, single oxides are also formed in the steel to a certain extent. Therefore, in order to improve the wear resistance of the steel after nitriding while ensuring the machinability of the steel, the present inventors have further studied the relationship between the inclusions in the steel and the machinability and wear resistance, focusing on the above-mentioned MnS-based inclusions (single MnS inclusions and MnS composite inclusions), single oxides, and MnS composite oxides. As a result, it has been found that, if the inclusions in the steel satisfy the following (I) to (III), the element contents of the chemical composition are within the ranges of this embodiment, and Fn1 and Fn2 are within the ranges of this embodiment, the machinability of the steel and the wear resistance of the crankshaft manufactured by nitriding the steel can be further improved.

[0031] (I) In the steel material, the total surface density of MnS single inclusions with an equivalent circle diameter of 5.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 5.0 μm or more is 20 pieces / mm 2 That's all. (II) In the steel material, the ratio of the total number of MnS single inclusions having an equivalent circle diameter of 1.0 μm or more and MnS composite inclusions having an equivalent circle diameter of 1.0 μm or more to the total number of inclusions having an equivalent circle diameter of 1.0 μm or more is 70% or more. (III) In the steel material, the ratio of the number of MnS composite oxides having an equivalent circle diameter of 1.0 μm or more to the total number of single oxides having an equivalent circle diameter of 1.0 μm or more and MnS composite oxides having an equivalent circle diameter of 1.0 μm or more is 30% or more.

[0032] As described above, the steel material and the crankshaft of the present embodiment were developed as a result of studies focusing on the chemical composition and inclusions that may be the starting points of cracks in the nitride layer (particularly the compound layer), and have the following configuration.

[0033] [1] A steel material, In mass%, C: 0.25%~0.35%, Si: 0.05 to 0.35%, Mn: 0.85-1.20%, P: 0.080% or less, S: 0.030~0.100%, Cr: 0.10% or less, Ti: 0.050% or less, Al: 0.050% or less, N: 0.005 to 0.024%, and O: 0.0100% or less, the balance being Fe and impurities, Fn1 defined by formula (1) is 1.00 to 2.05, Fn2 defined by formula (2) is 0.42 to 0.60, Among the inclusions in the steel material, An inclusion whose total Mn content and S content is 80.0% or more by mass% is defined as a single MnS inclusion. An inclusion whose total Mn content and S content is less than 15.0 to 80.0% by mass is defined as an MnS composite inclusion. An inclusion having an Al content, Ca content and O content of 80.0% or more by mass and an Mn content and S content of less than 15.0% by mass is defined as a single oxide. When the inclusions having an Al content, a Ca content, and an O content of 15.0 to less than 80.0% by mass and an Mn content and an S content of 15.0 to less than 80.0% by mass are defined as MnS composite oxides, In the steel material, The total surface density of the MnS single inclusions having an equivalent circle diameter of 5.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 5.0 μm or more is 20 pieces / mm 2 That's all. a ratio of the total number of the MnS single inclusions having an equivalent circle diameter of 1.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 1.0 μm or more to the total number of inclusions having an equivalent circle diameter of 1.0 μm or more is 70% or more; a ratio of the number of the MnS composite oxide having an equivalent circle diameter of 1.0 μm or more to the total number of the single oxide having an equivalent circle diameter of 1.0 μm or more and the MnS composite oxide having an equivalent circle diameter of 1.0 μm or more is 30% or more; Steel material. Fn1 = Mn + 7.24 Cr + 6.53 Al (1) Fn2=C+0.10Si+0.19Mn+0.23Cr-0.34S...(2) Here, the content of each element in formula (1) and formula (2) is substituted in mass % for each element symbol corresponding to the element.

[0034] [2] The steel material according to [1], Instead of a part of the Fe, Cu: 0.20% or less, Ni: 0.20% or less, Mo: 0.10% or less Nb: 0.050% or less, Ca: 0.0100% or less, Bi: 0.30% or less, Te: 0.0100% or less, Zr: 0.0100% or less, and Pb: 0.09% or less, Contains one or more elements selected from the group consisting of Steel material.

[0035] [3] A pin portion and The journal section and an arm portion disposed between the pin portion and the journal portion, At least the pin portion and the journal portion are A nitride layer formed on the surface; A core portion located inside the nitride layer, The core portion comprises, in mass%, C: 0.25%~0.35%, Si: 0.05 to 0.35%, Mn: 0.85-1.20%, P: 0.080% or less, S: 0.030~0.100%, Cr: 0.10% or less, Ti: 0.050% or less, Al: 0.050% or less, N: 0.005 to 0.024%, and O: 0.0100% or less, the balance being Fe and impurities, Fn1 defined by formula (1) is 1.00 to 2.05, Fn2 defined by formula (2) is 0.42 to 0.60, Among the inclusions in the core portion, An inclusion whose total Mn content and S content is 80.0% or more by mass% is defined as a single MnS inclusion. An inclusion whose total Mn content and S content is less than 15.0 to 80.0% by mass is defined as an MnS composite inclusion. An inclusion having an Al content, Ca content and O content of 80.0% or more by mass and an Mn content and S content of less than 15.0% by mass is defined as a single oxide. When the inclusions having an Al content, a Ca content, and an O content of 15.0 to less than 80.0% by mass and an Mn content and an S content of 15.0 to less than 80.0% by mass are defined as MnS composite oxides, In the core portion, The total surface density of the MnS single inclusions having an equivalent circle diameter of 5.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 5.0 μm or more is 20 pieces / mm 2 That's all. a ratio of the total number of the MnS single inclusions having an equivalent circle diameter of 1.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 1.0 μm or more to the total number of inclusions having an equivalent circle diameter of 1.0 μm or more is 70% or more; a ratio of the number of the MnS composite oxide having an equivalent circle diameter of 1.0 μm or more to the total number of the single oxide having an equivalent circle diameter of 1.0 μm or more and the MnS composite oxide having an equivalent circle diameter of 1.0 μm or more is 30% or more; Crankshaft. Fn1 = Mn + 7.24 Cr + 6.53 Al (1) Fn2=C+0.10Si+0.19Mn+0.23Cr-0.34S...(2) Here, the content of each element in formula (1) and formula (2) is substituted in mass % for each element symbol corresponding to the element.

[0036] [4] [3] A crankshaft according to the present invention, The core portion further contains, instead of a part of the Fe, Cu: 0.20% or less, Ni: 0.20% or less, Mo: 0.10% or less Nb: 0.050% or less, Ca: 0.0100% or less, Bi: 0.30% or less, Te: 0.0100% or less, Zr: 0.0100% or less, and Pb: 0.09% or less, Contains one or more elements selected from the group consisting of Crankshaft.

[0037] The steel material and the crankshaft of the present embodiment will be described below. Note that "%" for elements means mass% unless otherwise specified. In addition, in this specification, "nitriding treatment" includes soft nitriding treatment.

[0038] [Chemical composition] The steel material of this embodiment is used as a material for crankshafts. The chemical composition of the steel material of this embodiment contains the following elements.

[0039] C: 0.25% to 0.35% Carbon (C) increases the bending fatigue strength of the steel material (crankshaft) after nitriding. If the C content is less than 0.25%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the C content exceeds 0.35%, even if the contents of other elements are within the range of this embodiment, the hardness of the core of the crankshaft becomes too high and the hardness of the nitrided layer also becomes too high. In this case, the bending straightening property of the crankshaft decreases. Therefore, the C content is 0.25 to 0.35%. The preferable lower limit of the C content is 0.26%, and more preferably 0.27%.

[0040] Silicon: 0.05 to 0.35% Silicon (Si) increases the bending fatigue strength of the crankshaft. Si also deoxidizes the steel. If the Si content is less than 0.05%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Si content exceeds 0.35%, the hardness of the nitrided layer of the crankshaft becomes too high even if the contents of other elements are within the range of this embodiment, and the bending straightening ability of the crankshaft decreases. Therefore, the Si content is 0.05 to 0.35%. The preferred lower limit of the Si content is 0.07%, more preferably 0.09%, and more preferably 0.10%. The preferred upper limit of the Si content is 0.33%, more preferably 0.31%, and more preferably 0.30%.

[0041] Mn: 0.85-1.20% Manganese (Mn) increases the bending fatigue strength of the crankshaft. Mn also deoxidizes the steel. If the Mn content is less than 0.85%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mn content exceeds 1.20%, the hardness of the nitrided layer of the crankshaft becomes too high even if the contents of other elements are within the range of this embodiment, and the bending straightening ability of the crankshaft decreases. Therefore, the Mn content is 0.85 to 1.20%. The lower limit of the Mn content is preferably 0.87%, more preferably 0.89%, and even more preferably 0.90%. The upper limit of the Mn content is preferably 1.18%, more preferably 1.16%, and even more preferably 1.14%.

[0042] P:0.080% or less Phosphorus (P) is an unavoidably contained impurity. In other words, the P content is more than 0%. If the P content exceeds 0.080%, the bending fatigue strength of the crankshaft decreases even if the contents of other elements are within the range of this embodiment. Therefore, the P content is 0.080% or less. A preferable upper limit of the P content is 0.050%, and more preferably 0.030%. It is preferable that the P content is as low as possible. However, excessive reduction of the P content increases the manufacturing cost. Therefore, a preferable lower limit of the P content is 0.001%, and more preferably 0.002%.

[0043] S: 0.030~0.100% Sulfur (S) improves the machinability of steel. If the S content is less than 0.030%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the S content exceeds 0.100%, the castability of the steel decreases even if the contents of other elements are within the range of this embodiment. Therefore, the S content is 0.030 to 0.100%. The preferred lower limit of the S content is 0.035%, more preferably 0.037%, and even more preferably 0.040%. The preferred upper limit of the S content is 0.095%, more preferably 0.090%, more preferably 0.085%, and even more preferably 0.080%.

[0044] Cr:0.10% or less Chromium (Cr) is an unavoidably contained impurity. In other words, the Cr content is more than 0%. If the Cr content exceeds 0.10%, the straightening property of the crankshaft decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Cr content is 0.10% or less. It is preferable that the Cr content is as low as possible. However, excessive reduction of the Cr content increases the manufacturing cost. Therefore, the preferable lower limit of the Cr content is 0.01%, and more preferably 0.02%.

[0045] Ti: 0.050% or less Titanium (Ti) is inevitably contained. That is, the Ti content is more than 0%. Ti combines with N to form TiN, which suppresses the coarsening of crystal grains through a pinning effect, thereby increasing the bending fatigue strength of the crankshaft. If even a small amount of Ti is contained, the above effect can be obtained to a certain extent. However, if the Ti content exceeds 0.050%, coarse TiN is formed and the bending fatigue strength of the crankshaft decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Ti content is 0.050% or less. The preferred lower limit of the Ti content is 0.001%, more preferably 0.003%, and even more preferably 0.005%. The preferred upper limit of the Ti content is 0.045%, more preferably 0.040%, and even more preferably 0.030%.

[0046] Al: 0.050% or less Aluminum (Al) is inevitably contained. That is, the Al content is more than 0%. Al combines with nitrogen during nitriding to form AlN, which increases the hardness of the nitrided layer of the crankshaft and increases the bending fatigue strength of the crankshaft. If even a small amount of Al is contained, the above effect can be obtained to a certain extent. However, if the Al content exceeds 0.050%, even if the contents of other elements are within the range of this embodiment, the hardness of the nitrided layer of the crankshaft becomes too high, and the bending straightening ability of the crankshaft decreases. Therefore, the Al content is 0.050% or less. The preferred upper limit of the Al content is 0.045%, more preferably 0.040%, more preferably 0.035%, and more preferably 0.030%. The preferred lower limit of the Al content is 0.001%, more preferably 0.002%, and more preferably 0.005%. The Al content here means the content of Al (total Al) including oxides in the steel.

[0047] N: 0.005~0.024% Nitrogen (N) combines with Ti to form TiN, which inhibits the coarsening of crystal grains through a pinning effect, thereby enhancing the bending fatigue strength of the crankshaft. If the N content is less than 0.005%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the N content exceeds 0.024%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the N content is 0.005 to 0.024%. The preferred lower limit of the N content is 0.006%, more preferably 0.008%, and even more preferably 0.010%. The preferred upper limit of the N content is 0.022%, more preferably 0.021%, and even more preferably 0.020%.

[0048] O: 0.0100% or less Oxygen (O) is an impurity that is inevitably contained. That is, the O content is more than 0%. O generates oxides in the steel material. If the O content exceeds 0.0100%, even if the contents of other elements are within the range of this embodiment, coarse oxides are generated, and the bending fatigue strength of the crankshaft decreases, and the wear resistance also decreases. Therefore, the O content is 0.0100% or less. A preferable upper limit of the O content is 0.0080%, more preferably 0.0060%, and even more preferably 0.0050%. It is preferable that the O content is as low as possible. However, excessive reduction of the O content increases the manufacturing cost. Therefore, a preferable lower limit of the O content is 0.0001%, and even more preferably 0.0005%.

[0049] The balance of the chemical composition of the steel material of this embodiment is composed of Fe and impurities. Here, the impurities refer to components that are mixed in from raw materials such as ore, scrap, or the manufacturing environment when the steel material is industrially manufactured, and are not intentionally contained in the steel material. Examples of such impurities include the following: Co: 0.02% or less, Sn: 0.02% or less, Zn: 0.02% or less.

[0050] [Optional elements] [Group 1 arbitrary elements] The chemical composition of the steel material of this embodiment may further contain one or more elements selected from the group consisting of Cu, Ni, Mo, and Nb in place of a portion of Fe. These elements are optional elements, and all of them increase the bending fatigue strength of the crankshaft.

[0051] Cu:0.20% or less Copper (Cu) is an optional element and may not be contained. That is, the Cu content may be 0%. When it is contained, that is, when the Cu content is more than 0%, Cu dissolves in the steel material and increases the bending fatigue strength of the crankshaft. If even a small amount of Cu is contained, the above effect can be obtained to a certain degree. However, if the Cu content exceeds 0.20%, the bending straightening property of the crankshaft decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Cu content is 0.20% or less. That is, the Cu content is 0 to 0.20%. The preferred lower limit of the Cu content is more than 0%, more preferably 0.01%, more preferably 0.02%, more preferably 0.05%, and more preferably 0.07%. The preferred upper limit of the Cu content is 0.19%, more preferably 0.18%, and more preferably 0.17%.

[0052] Ni: 0.20% or less Nickel (Ni) is an optional element and may not be contained. That is, the Ni content may be 0%. When it is contained, that is, when the Ni content is more than 0%, Ni dissolves in the steel material and increases the bending fatigue strength of the crankshaft. If even a small amount of Ni is contained, the above effect can be obtained to a certain extent. However, if the Ni content exceeds 0.20%, the bending straightening property of the crankshaft decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Ni content is 0.20% or less. That is, the Ni content is 0 to 0.20%. The preferable lower limit of the Ni content is more than 0%, more preferably 0.01%, more preferably 0.02%, more preferably 0.05%, and more preferably 0.07%. The preferable upper limit of the Ni content is 0.19%, more preferably 0.18%, and more preferably 0.17%.

[0053] Mo: 0.10% or less Molybdenum (Mo) is an optional element and may not be contained. That is, the Mo content may be 0%. When it is contained, that is, when the Mo content is more than 0%, Mo dissolves in the steel material and increases the bending fatigue strength of the crankshaft. If even a small amount of Mo is contained, the above effect can be obtained to a certain degree. However, if the Mo content exceeds 0.20%, the bending straightening property of the crankshaft decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Mo content is 0.10% or less. That is, the Mo content is 0 to 0.10%. The preferred lower limit of the Mo content is more than 0%, more preferably 0.01%, more preferably 0.02%, and even more preferably 0.03%. The preferred upper limit of the Mo content is 0.09%, and more preferably 0.08%.

[0054] Nb: 0.050% or less Niobium (Nb) is an optional element and may not be contained. That is, the Nb content may be 0%. When it is contained, that is, when the Nb content is more than 0%, Nb forms carbides, nitrides, or carbonitrides, refines crystal grains by a pinning effect, and increases the bending fatigue strength of the crankshaft. If even a small amount of Nb is contained, the above effect can be obtained to a certain extent. However, if the Nb content exceeds 0.050%, the bending straightening property of the crankshaft decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Nb content is 0.050% or less. That is, the Nb content is 0 to 0.050%. The preferable lower limit of the Nb content is more than 0%, more preferably 0.001%, more preferably 0.003%, and more preferably 0.005%. The preferable upper limit of the Nb content is 0.040%, and more preferably 0.030%.

[0055] [Group 2 arbitrary elements] The steel material of the present embodiment may further contain one or more elements selected from the group consisting of Ca, Bi, Te, Zr, and Pb in place of a portion of Fe. These elements are optional elements, and all of them improve the machinability of the steel material.

[0056] Ca:0.0100% or less Calcium (Ca) is an optional element and may not be contained. That is, the Ca content may be 0%. When it is contained, that is, when the Ca content is more than 0%, Ca enhances the machinability of the steel material. If even a small amount of Ca is contained, the above effect can be obtained to some extent. However, if the Ca content exceeds 0.0100%, even if the contents of other elements are within the range of this embodiment, coarse oxides are formed, and the bending fatigue strength of the crankshaft decreases. Therefore, the Ca content is 0.0100% or less. That is, the Ca content is 0 to 0.0100%. The preferred lower limit of the Ca content is more than 0%, more preferably 0.0001%, more preferably 0.0002%, and more preferably 0.0003%. The preferred upper limit of the Ca content is 0.0090%, and more preferably 0.0080%.

[0057] Bi:0.30% or less Bismuth (Bi) is an optional element and may not be contained. That is, the Bi content may be 0%. When it is contained, that is, when the Bi content is more than 0%, Bi enhances the machinability of the steel material. If even a small amount of Bi is contained, the above effect can be obtained to some extent. However, if the Bi content exceeds 0.30%, the bending fatigue strength of the crankshaft decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Bi content is 0.30% or less. That is, the Bi content is 0 to 0.30%. The preferred lower limit of the Bi content is more than 0%, more preferably 0.01%, more preferably 0.02%, and even more preferably 0.05%. The preferred upper limit of the Bi content is 0.27%, and more preferably 0.25%.

[0058] Te: 0.0100% or less Tellurium (Te) is an optional element and may not be contained. That is, the Te content may be 0%. When it is contained, that is, when the Te content is more than 0%, Te enhances the machinability of the steel material. If even a small amount of Te is contained, the above effect can be obtained to some extent. However, if the Te content exceeds 0.0100%, the bending fatigue strength of the crankshaft decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Te content is 0.0100% or less. That is, the Te content is 0 to 0.0100%. The preferred lower limit of the Te content is more than 0%, more preferably 0.0001%, more preferably 0.0002%, and even more preferably 0.0003%. The preferred upper limit of the Te content is 0.0090%, and more preferably 0.0080%.

[0059] Zr: 0.0100% or less Zirconium (Zr) is an optional element and may not be contained. That is, the Zr content may be 0%. When contained, that is, when the Zr content is more than 0%, Zr enhances the machinability of the steel material. If even a small amount of Zr is contained, the above effect can be obtained to some extent. However, if the Zr content exceeds 0.0100%, the bending fatigue strength of the crankshaft decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Zr content is 0.0100% or less. That is, the Zr content is 0 to 0.0100%. The preferable lower limit of the Zr content is more than 0%, more preferably 0.0001%, more preferably 0.0002%, and more preferably 0.0003%. The preferable upper limit of the Zr content is 0.0090%, and more preferably 0.0080%.

[0060] Pb: 0.09% or less Lead (Pb) is an optional element and may not be contained. That is, the Pb content may be 0%. When it is contained, that is, when the Pb content is more than 0%, Pb enhances the machinability of the steel material. If even a small amount of Pb is contained, the above effect can be obtained to a certain degree. However, if the Pb content exceeds 0.09%, the bending fatigue strength of the crankshaft decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Pb content is 0.09% or less. That is, the Pb content is 0 to 0.09%. The preferred lower limit of the Pb content is more than 0%, more preferably 0.01%, more preferably 0.02%, and even more preferably 0.05%. The preferred upper limit of the Pb content is 0.08%, and more preferably 0.07%.

[0061] [About Fn1 and Fn2] The chemical composition of the steel material of this embodiment further has Fn1 defined by formula (1) of 1.00 to 2.05, and Fn2 defined by formula (2) of 0.42 to 0.60%, provided that the content of each element in the chemical composition is within the range of this embodiment. Fn1 = Mn + 7.24 Cr + 6.53 Al (1) Fn2=C+0.10Si+0.19Mn+0.23Cr-0.34S...(2) Here, the content of each element in formula (1) and formula (2) is substituted in mass % for each element symbol corresponding to the element.

[0062] [About Fn1] Fn1 defined by formula (1) is an index of the hardness of the nitrided layer formed on the surface layer of the steel material (crankshaft) after nitriding, on the premise that the content of each element in the chemical composition is within the range of this embodiment, and Fn2 is within the range of this embodiment. Therefore, in a steel material in which the content of each element in the chemical composition is within the range of this embodiment, Fn1 is related to the bending fatigue strength of the crankshaft and the bending straightening property of the crankshaft. Specifically, if Fn1 is less than 1.00, even if the content of each element in the chemical composition is within the range of this embodiment and Fn2 is within the range of this embodiment, the bending fatigue strength of the crankshaft is not sufficient. On the other hand, if Fn1 exceeds 2.05, even if the content of each element in the chemical composition is within the range of this embodiment and Fn2 is within the range of this embodiment, the bending straightening property of the crankshaft is reduced. If Fn1 is 1.00 to 2.05, on the premise that the content of each element in the chemical composition is within the range of this embodiment and Fn2 is within the range of this embodiment, the bending fatigue strength of the crankshaft is sufficient and the bending straightening property of the crankshaft is also sufficiently improved. The lower limit of Fn1 is preferably 1.02, and more preferably 1.03. The upper limit of Fn1 is preferably 2.03, and more preferably 2.01, and even more preferably 2.00.

[0063] [About Fn2] Fn2 defined by formula (2) is an index of hardness of the steel material (that is, the core part of the crankshaft) before nitriding, on the premise that the content of each element in the chemical composition is within the range of this embodiment, and Fn1 is within the range of this embodiment. Therefore, in a steel material in which the content of each element in the chemical composition is within the range of this embodiment, Fn2 is related to the bending fatigue strength of the crankshaft and the machinability of the steel material. Specifically, if Fn2 is less than 0.42, even if the content of each element in the chemical composition is within the range of this embodiment and Fn1 is within the range of this embodiment, the crankshaft cannot obtain sufficient bending fatigue strength. On the other hand, if Fn2 exceeds 0.60, even if the content of each element in the chemical composition is within the range of this embodiment and Fn1 is within the range of this embodiment, the steel material cannot obtain sufficient machinability. If Fn2 is 0.42 to 0.60, on the premise that the content of each element in the chemical composition is within the range of this embodiment and Fn1 is within the range of this embodiment, the crankshaft can obtain sufficient bending fatigue strength, and the machinability of the steel material is also sufficiently improved. The lower limit of Fn2 is preferably 0.43, more preferably 0.44, and even more preferably 0.45. The upper limit of Fn2 is preferably 0.58, more preferably 0.57, and even more preferably 0.56.

[0064] [About inclusions in steel] In the steel material of this embodiment, the following definitions are given. (a) When the mass percentage of inclusions is taken as 100%, an inclusion with a total content of Mn and S of 80.0% or more by mass is defined as a "single MnS inclusion". (b) When the mass percent of inclusions is taken as 100%, inclusions whose total content of Mn and S is, in mass percent, 15.0 to less than 80.0% are defined as "MnS composite inclusions". (c) When the mass percent of the inclusions is 100%, an inclusion whose total content of Al, Ca, and O is 80.0% or more by mass, and whose total content of Mn and S is less than 15.0% by mass, is defined as a "single oxide." (d) When the mass percent of inclusions is 100%, the inclusions having a total Mn and S content of 15.0 to less than 80.0% by mass and a total Al, Ca and O content of 15.0 to less than 80.0% by mass are defined as "MnS composite oxides". As defined above, the MnS composite oxide is included in the MnS composite inclusions.

[0065] In the steel material of this embodiment, the inclusions satisfy the following requirements. (I) In the steel material, the total areal density of MnS single inclusions with a circle equivalent diameter of 5.0 μm or more and MnS composite inclusions with a circle equivalent diameter of 5.0 μm or more is 20 pieces / mm 2 That's all. (II) In the steel material, the ratio of the total number of MnS single inclusions having an equivalent circle diameter of 1.0 μm or more and MnS composite inclusions having an equivalent circle diameter of 1.0 μm or more to the total number of inclusions having an equivalent circle diameter of 1.0 μm or more is 70% or more. (III) In the steel material, the ratio of the number of MnS composite oxides having an equivalent circle diameter of 1.0 μm or more to the total number of single oxides having an equivalent circle diameter of 1.0 μm or more and MnS composite oxides having an equivalent circle diameter of 1.0 μm or more is 30% or more. Below, (I) to (III) will be explained.

[0066] [Regarding (I)] MnS inclusions alone and MnS compound inclusions are defined as "MnS-based inclusions". MnS-based inclusions improve the machinability of steel materials. Therefore, the surface density (pieces / mm 2 ) is higher, the machinability of the steel material is improved. However, if the size of the MnS-based inclusions is too small, they do not contribute to improving the machinability of the steel material. In the case of a steel material having a chemical composition in which the above-mentioned element contents are within the ranges of this embodiment and Fn1 and Fn2 are within the ranges of this embodiment, MnS-based inclusions having an equivalent circle diameter of less than 5.0 μm are unlikely to contribute to improving the machinability of the steel material. On the other hand, MnS-based inclusions having an equivalent circle diameter of 5.0 μm or more significantly improve the machinability of the steel material.

[0067] The surface density of MnS-based inclusions (single MnS inclusions and MnS compound inclusions) with a circle equivalent diameter of 5.0 μm or more is defined as surface density SN (pieces / mm 2 ) is defined as the surface density SN of 20 pieces / mm 2 If the content of each of the above elements is within the range of this embodiment, and Fn1 and Fn2 are within the range of this embodiment, the machinability of the steel material having the chemical composition can be sufficiently improved. 2 and more preferably 25 pieces / mm 2 The upper limit of the areal density of MnS-based inclusions having a circle-equivalent diameter of 5.0 μm or more is not particularly limited, but in the case of a steel material having a chemical composition in which the above-mentioned element contents are within the ranges of this embodiment and Fn1 and Fn2 are within the ranges of this embodiment, the upper limit of the areal density of MnS-based inclusions having a circle-equivalent diameter of 5.0 μm or more is, for example, 250 pieces / mm 2 and preferably 200 pieces / mm 2 In the present embodiment, the upper limit of the circle-equivalent diameter of the inclusions is not particularly limited. However, in the case of a steel material having a chemical composition in which the above-mentioned contents of each element are within the ranges of the present embodiment and Fn1 and Fn2 are within the ranges of the present embodiment, the upper limit of the circle-equivalent diameter of the MnS-based inclusions is, for example, 75 μm.

[0068] [Regarding (II)] The crankshaft of this embodiment has a nitride layer on the surface. The nitride layer is formed to a predetermined depth from the surface of the steel material by nitriding. The nitride layer has a compound layer and a diffusion layer. The compound layer is formed in a range of a predetermined depth from the surface of the nitride layer. The diffusion layer is formed inside the steel material than the compound layer. In the crankshaft, the inside of the nitride layer is called the core. Here, inclusions are present in the region of the steel material before nitriding where the compound layer is formed. Therefore, inclusions naturally remain in the compound layer after nitriding. Among the inclusions contained in the compound layer, oxides are likely to become the starting point of cracks in the compound layer of the pin and journal parts of the crankshaft during use of the crankshaft. Therefore, oxides reduce the wear resistance of the crankshaft. Therefore, if the ratio of the total number of MnS-based inclusions to the total number of inclusions in the steel material is increased, the ratio of the number of oxides can be reduced, and the wear resistance of the pin and journal parts of the crankshaft is improved.

[0069] Here, the ratio of the total number of MnS single inclusions and MnS composite inclusions to the total number of inclusions with a circle equivalent diameter of 1.0 μm or more is defined as the "MnS inclusion number ratio RA MnS " Inclusions with an equivalent circle diameter of less than 1.0 μm do not have a significant effect on the wear resistance of crankshafts equipped with a nitrided layer (compound layer). On the other hand, inclusions with an equivalent circle diameter of 1.0 μm or more may affect the wear resistance of crankshafts equipped with a nitrided layer (compound layer). Therefore, the number ratio RA of MnS-based inclusions is MnS The inclusions to be inspected have a circle-equivalent diameter of 1.0 μm or more. In this embodiment, the upper limit of the circle-equivalent diameter of the inclusions is not particularly limited. However, in the case of a steel material having a chemical composition in which the contents of the above-mentioned elements are within the ranges of this embodiment and Fn1 and Fn2 are within the ranges of this embodiment, the upper limit of the circle-equivalent diameter of the inclusions is, for example, 75 μm.

[0070] In a steel material having a chemical composition in which the contents of the above-mentioned elements are within the ranges of this embodiment and Fn1 and Fn2 are within the ranges of this embodiment, the ratio of the total number of MnS inclusions and MnS composite inclusions to the total number of inclusions having a circle equivalent diameter of 1.0 μm or more (i.e., the ratio of the number of MnS-based inclusions RA MnS If the ratio of MnS-based inclusions is 70% or more, the wear resistance of the crankshaft can be sufficiently improved. MnS The lower limit of the ratio of the number of MnS-based inclusions RA is preferably more than 70%, more preferably 72%, and even more preferably 73%. MnS The upper limit is not particularly limited and may be 100%.

[0071] [Regarding (III)] In this specification, the term "oxide" is used to collectively refer to both single oxides and MnS composite oxides. In the above-mentioned crankshaft, even if the number ratio of MnS-based inclusions among all inclusions is high, if the number ratio of MnS composite oxides among the oxides is low, the number ratio of single oxides among the oxides will be high. In this case, the proportion of hard single oxides present in the compound layer will be high. Single inclusions are likely to become the starting point of cracks in the compound layer. Therefore, if the proportion of single oxides among the oxides present in the compound layer is high, the wear resistance of the crankshaft having a nitrided layer will decrease. Therefore, the number ratio RA of MnS-based inclusions MnS In addition to increasing the number of MnS complex oxides, increasing the ratio of the number of MnS complex oxides to the total number of oxides (single oxides and MnS complex oxides) increases the wear resistance of the crankshaft having a nitrided layer.

[0072] The ratio of the number of MnS composite oxides with a circle equivalent diameter of 1.0 μm or more to the total number of oxides (single oxides and MnS composite oxides) with a circle equivalent diameter of 1.0 μm or more in the steel material is called the MnS composite oxide number ratio RA. OXIn a steel material having a chemical composition in which the above-mentioned contents of each element are within the range of this embodiment and Fn1 and Fn2 are within the range of this embodiment, while satisfying the above (I) and (II), the ratio of the number of MnS composite oxides having a circle equivalent diameter of 1.0 μm or more to the total number of oxides (single oxides and MnS composite oxides) having a circle equivalent diameter of 1.0 μm or more in the steel material (MnS composite oxide number ratio RA OX If the ratio of the number of MnS complex oxides RA is 30% or more, sufficient wear resistance can be obtained in the crankshaft. OX The lower limit of the ratio by number of MnS composite oxides RA is preferably 32.0%, more preferably 34.0%, and even more preferably 35.0%. OX The upper limit of is not particularly limited and may be 100.0%. In this embodiment, the upper limit of the equivalent circle diameter of the oxide is not particularly limited. However, in the case of a steel material having a chemical composition in which the above-mentioned contents of each element are within the range of this embodiment and Fn1 and Fn2 are within the range of this embodiment, the upper limit of the equivalent circle diameter of the oxide is, for example, 75 μm.

[0073] [Method of measuring inclusions] Surface number density SN, MnS inclusion number ratio RA MnS , MnS complex oxide number ratio RA OX can be calculated in the following way:

[0074] The number of MnS-based inclusions (single MnS inclusions and MnS composite inclusions) and the number of oxides (single oxides and MnS composite oxides) in steel can be measured by the following method. A sample is taken from the steel material. Specifically, as shown in FIG. 1, a sample is taken from a position R / 2 (R is the radius of the steel material 1) in the radial direction from the central axis C1 of the steel material 1. The size of the observation surface of the sample is not particularly limited. The observation surface of the sample is, for example, L1×L2, where L1 is 10 mm and L2 is 5 mm. The sample thickness L3, which is the direction perpendicular to the observation surface, is, for example, 5 mm. The normal N of the observation surface is perpendicular to the central axis C1 (i.e., the observation surface is parallel to the axial direction of the steel material), and the R / 2 position is approximately the center position of the observation surface.

[0075] The observation surface of the collected sample is mirror-polished, and 50 fields of view (field area per field: 125 μm × 75 μm) are randomly observed at 2000x magnification using a scanning electron microscope (SEM).

[0076] The inclusions in each field of view are identified. Inclusions can be identified by their contrast. Energy dispersive X-ray spectroscopy (EDX) is used to identify each identified inclusion as either a single MnS inclusion, a MnS composite inclusion, a single oxide, or a MnS composite oxide. Specifically, a beam is irradiated onto each inclusion in the field of view to detect characteristic X-rays and perform elemental analysis of the inclusion. Based on the results of the elemental analysis of each inclusion, the inclusion is identified as follows:

[0077] (a) When the mass percent of an inclusion is taken as 100%, if the sum of the Mn content and S content in the inclusion is 80.0% or more by mass, the inclusion is defined as a "single MnS inclusion." (b) When the mass percent of an inclusion is taken as 100%, if the sum of the Mn content and S content in the inclusion is 15.0 to less than 80.0% by mass, the inclusion is defined as a "MnS composite inclusion." (c) When the mass percent of an inclusion is taken as 100%, and the sum of the Al content, Ca content, and O content in the inclusion is 80.0% or more, and the sum of the Mn content and S content is less than 15.0%, the inclusion is defined as a "single oxide". (d) When the mass percent of an inclusion is taken as 100%, if the sum of the Al content, Ca content, and O content in the inclusion is from 15.0 to less than 80.0% by mass, and the sum of the Mn content and S content is from 15.0 to less than 80.0% by mass, the inclusion is defined as a "MnS composite oxide".

[0078] The inclusions to be identified are those with an equivalent circle diameter of 1.0 μm or more. Here, the equivalent circle diameter means the diameter of a circle when the area of ​​each inclusion is converted into a circle having the same area. The equivalent circle diameter (μm) of each identified inclusion is determined by well-known image analysis.

[0079] In this embodiment, the EDX beam diameter used to identify inclusions is about 50 nm. As a result, for inclusions with an equivalent circle diameter of less than 1.0 μm, the components of the base steel are detected by EDX, and the accuracy of elemental analysis may not be sufficient. Inclusions with an equivalent circle diameter of less than 1.0 μm have even less effect on machinability and wear resistance. Therefore, in this embodiment, as described above, inclusions with an equivalent circle diameter of 1.0 μm or more are identified.

[0080] Among the inclusions identified in the 50 visual fields, the total number of MnS single inclusions with an equivalent circle diameter of 5.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 5.0 μm or more (i.e., MnS-based inclusions with an equivalent circle diameter of 5.0 μm or more) is calculated. Based on the total number of MnS-based inclusions with an equivalent circle diameter of 5.0 μm or more and the total area of ​​the 50 visual fields, the surface number density SN (pieces / mm 2 The surface density SN is calculated by rounding off the first decimal place.

[0081] Furthermore, among the inclusions identified in the 50 visual fields, the total number of inclusions with an equivalent circle diameter of 1.0 μm or more is calculated. Furthermore, among the inclusions identified in the 50 visual fields, the total number of MnS single inclusions with an equivalent circle diameter of 1.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 1.0 μm or more is calculated. Based on the total number of inclusions with an equivalent circle diameter of 1.0 μm or more and the total number of MnS single inclusions with an equivalent circle diameter of 1.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 1.0 μm or more, the number ratio RA of MnS-based inclusions is calculated by the following formula: MnS Calculate the percentage. RA MnS = (Total number of MnS single inclusions with an equivalent circle diameter of 1.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 1.0 μm or more) / (Total number of inclusions with an equivalent circle diameter of 1.0 μm or more) × 100 The ratio of MnS inclusions to the number of MnS shall be the value obtained by rounding off to the first decimal place.

[0082] Furthermore, among the inclusions identified in the 50 visual fields, the total number of single oxides having an equivalent circle diameter of 1.0 μm or more and MnS composite oxides having an equivalent circle diameter of 1.0 μm or more is calculated. Furthermore, among the inclusions identified in the 50 visual fields, the total number of MnS composite oxides having an equivalent circle diameter of 1.0 μm or more is calculated. Based on the total number of single oxides having an equivalent circle diameter of 1.0 μm or more and MnS composite oxides having an equivalent circle diameter of 1.0 μm or more (i.e., the total number of oxides having an equivalent circle diameter of 1.0 μm or more) and the total number of MnS composite oxides having an equivalent circle diameter of 1.0 μm or more, the MnS composite oxide number ratio RA is calculated by the following formula: OX Calculate the percentage. RA OX = (total number of MnS composite oxides with a circle equivalent diameter of 1.0 μm or more) / (total number of oxides with a circle equivalent diameter of 1.0 μm or more) × 100 The ratio of MnS complex oxide particles RA OX shall be the value obtained by rounding off to the first decimal place.

[0083] As described above, the steel material of this embodiment has each element within the range of this embodiment, Fn1 defined by formula (1) is 1.00 to 2.05, Fn2 defined by formula (2) is 0.42 to 0.60, and further satisfies the following (I) to (III). (I) In the steel material, the total surface density of MnS single inclusions with an equivalent circle diameter of 5.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 5.0 μm or more is 20 pieces / mm 2 That's all. (II) In the steel material, the ratio of the total number of MnS single inclusions having an equivalent circle diameter of 1.0 μm or more and MnS composite inclusions having an equivalent circle diameter of 1.0 μm or more to the total number of inclusions having an equivalent circle diameter of 1.0 μm or more is 70% or more. (III) In the steel material, the ratio of the number of MnS composite oxides having an equivalent circle diameter of 1.0 μm or more to the total number of single oxides having an equivalent circle diameter of 1.0 μm or more and MnS composite oxides having an equivalent circle diameter of 1.0 μm or more is 30% or more.

[0084] By virtue of having the above-described configuration, the steel material of this embodiment has excellent machinability, and furthermore, when the steel material is subjected to a nitriding treatment to be made into a crankshaft, excellent wear resistance, excellent bending fatigue strength, and excellent bending straightenability are obtained.

[0085] [About the crankshaft] The crankshaft of this embodiment is manufactured by hot forging the steel material of this embodiment and then carrying out a nitriding treatment. FIG. 2 is a diagram showing an example of a main part of the crankshaft of this embodiment. Referring to FIG. 2, the crankshaft 10 of this embodiment includes a pin portion 11, a journal portion 12, and an arm portion 13. The journal portion 12 is arranged coaxially with the rotation axis of the crankshaft 10. The pin portion 11 is arranged offset from the rotation axis of the crankshaft 10. The arm portion 13 is arranged between the pin portion 11 and the journal portion 12, and is connected to the pin portion 11 and the journal portion 12. The crankshaft 10 may include a fillet portion (not shown) in the adjacent portion of the pin portion 11 and the arm portion 13, or may include a fillet portion (not shown) in the adjacent portion of the journal portion 12 and the arm portion 13.

[0086] The journal portion 12 is rotatably supported by a bearing (not shown) and is connected to a drive source such as an engine. The pin portion 11 is inserted into the big end of a connecting rod (not shown). When the crankshaft 10 receives driving force from the drive source and rotates around its axis, the connecting rod moves up and down. At this time, the pin portion 11 and journal portion 12 slide while receiving an external force.

[0087] 3 is a cross-sectional view of the vicinity of the surface layer of the pin portion 11 or the journal portion 12 of the crankshaft 10 in FIG. 2. At least the pin portion 11 and the journal portion 12 of the crankshaft 10 include a nitride layer 20 formed on the surface layer and a core portion 23 inside the nitride layer 20. The nitride layer 20 is formed by nitriding and includes a compound layer 21 and a diffusion layer 22. The compound layer 21 is formed on the outermost surface layer of the crankshaft 10 and includes an ε phase which is an Fe nitride. The diffusion layer 22 is formed inside the compound layer and is reinforced by solid solution N and / or nitrides such as Al nitrides, Cr nitrides, and Mo nitrides. The core portion 23 is a base material portion inside the nitride layer 20 and is a portion not affected by the nitriding.

[0088] The depth of the nitride layer 20 can be appropriately adjusted by adjusting the conditions of the nitriding process.

[0089] [Chemical composition of the core] The chemical composition of the core of the pin and journal parts of the crankshaft is the same as that of the steel material of this embodiment, that is, the chemical composition of the core of the crankshaft is, in mass%, C: 0.25% to 0.35%, Si: 0.05 to 0.35%, Mn: 0.85 to 1.20%, P: 0.080% or less, S: 0.030 to 0.100%, Cr: 0.10% or less, Ti: 0.050% or less, Al: 0.050% or less, N: 0.005 to 0.024%, O: 0.0100% or less, Cu: 0 to 0.20%. , Ni: 0-0.20%, Mo: 0-0.10%, Nb: 0-0.050%, Ca: 0-0.0100%, Bi: 0-0.30%, Te: 0-0.0100%, Zr: 0-0.0100%, Pb: 0-0.09%, and the balance being Fe and impurities, Fn1 defined by formula (1) is 1.00-2.05, and Fn2 defined by formula (2) is 0.42-0.60.

[0090] The core further satisfies the following (I) to (III). (I) In the core, the surface number density (SN) of MnS single inclusions with a circle equivalent diameter of 5.0 μm or more and MnS composite inclusions with a circle equivalent diameter of 5.0 μm or more is 20 pieces / mm 2 That's all. (II) In the core, the ratio of the total number of MnS single inclusions with an equivalent circle diameter of 1.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 1.0 μm or more to the total number of inclusions with an equivalent circle diameter of 1.0 μm or more (i.e., the ratio of MnS-based inclusions, RA MnS ) is more than 70%. (III) In the core, the ratio of the number of MnS composite oxides having a circle equivalent diameter of 1.0 μm or more to the total number of oxides (single oxides and MnS composite oxides) having a circle equivalent diameter of 1.0 μm or more (i.e., the ratio of the number of MnS composite oxides RA OX ) is 30% or more.

[0091] The conditions (I) to (III) at the core of the pin and journal of the crankshaft are the same as those (I) to (III) for the steel material. Therefore, the preferable lower limit of the surface density SN at the core and the number ratio RA of MnS-based inclusions are MnS The preferable lower limit of the number ratio of MnS composite oxides RA OX The preferable lower limit of the surface density SN of the steel material and the preferable lower limit of the number ratio RA of MnS-based inclusions are MnS The preferable lower limit of the number ratio of MnS composite oxides RA OX This is the same as the preferred lower limit value of

[0092] [Manufacturing method] An example of a method for manufacturing the steel material of this embodiment and an example of a method for manufacturing the crankshaft will be described below. Note that as long as the steel material and the crankshaft of this embodiment have the above configuration, the manufacturing method is not limited to the manufacturing method described below. However, the manufacturing method described below is a suitable example for manufacturing the steel material and the crankshaft of this embodiment.

[0093] First, an example of a method for producing a steel material according to the present embodiment will be described. The example of the method for producing a steel material includes a steelmaking process and a hot working process. Each process will be described below.

[0094] [Steel manufacturing process] The steelmaking process includes a refining process and a continuous casting process.

[0095] [Refining process] In the refining process, primary refining is carried out using a converter, and then secondary refining is carried out using an LF (Ladle Furnace) and an RH (Ruhrstahl-Hausen).

[0096] [Primary Refining] In the refining process, first, molten pig iron produced by a known method is subjected to known molten pig iron pretreatment, followed by desulfurization, desiliconization, and dephosphorization. The desulfurized, desiliconized, and dephosphorized molten pig iron is refined (primary refining) using a converter to produce molten steel. During or after the primary refining, alloy elements may be added to the molten steel to adjust the composition of the molten steel.

[0097] [Secondary Refining] The molten steel after the primary refining is subjected to secondary refining. In the secondary refining, refining is performed in an LF, and then a RH vacuum degassing treatment is performed so that the morphology of the inclusions in the steel satisfies (I) to (III).

[0098] [Refining in LF] In the secondary refining, first, desulfurization is performed using LF, and then inclusions in the molten steel are removed. LF refining is operated to satisfy the following conditions: (i) The oxygen content of the molten steel during refining in the LF should be kept below 40 ppm. (ii) The temperature of the molten steel during refining in the LF is increased to 1550°C or higher.

[0099] [Regarding condition (i)] The oxygen content and temperature of the molten steel during refining in the LF affect the morphology of MnS-based inclusions. If the oxygen content in the molten steel during refining in the LF exceeds 40 ppm, coarse, massive MnS-based inclusions crystallize even if the molten steel temperature is 1550°C or higher. In this case, the massive MnS-based inclusions float to the surface and are absorbed into the slag, and the number of MnS-based inclusions (single MnS inclusions and MnS compound inclusions) in the steel product decreases. Alternatively, the MnS-based inclusions remain in the steel as coarse inclusions, and the number of MnS-based inclusions in the steel product decreases. As a result, the surface number density (SN) of MnS-based inclusions with a circle equivalent diameter of 5.0 μm or more in the steel product is 20 pieces / mm 2 It will be less than.

[0100] [Regarding condition (ii)] Similarly, if the molten steel temperature during refining in the LF is less than 1550°C, coarse, aggregated MnS-based inclusions will crystallize even if the oxygen content of the molten steel is 40 ppm or less. In this case, the aggregated MnS-based inclusions float to the surface and are absorbed into the slag, or the MnS-based inclusions remain in the steel in a coarse form, decreasing the number of MnS-based inclusions in the finished steel product. As a result, the surface number density (SN) of MnS-based inclusions with a circle equivalent diameter of 5.0 μm or more in the steel product is 20 pieces / mm 2 It will be less than.

[0101] The crystallization of MnS-based inclusions during refining at the LF is suppressed by adjusting the oxygen content of the molten steel during refining at the LF to 40 ppm or less and adjusting the temperature of the molten steel during refining at the LF to 1550° C. or more. Note that, during refining at the LF, alloy elements may be added to the molten steel to adjust the composition.

[0102] [RH vacuum degassing treatment] After refining in the LF, RH (Ruhrstahl-Hausen) vacuum degassing is performed to remove N and H from the molten steel and to separate and remove inclusions. In the RH vacuum degassing, alloy elements are added to the molten steel to adjust the composition as necessary. The RH vacuum degassing is operated to satisfy the following conditions (iii) to (v). (iii) The temperature of the molten steel during the RH vacuum degassing treatment is kept at 1550°C or higher. (iv) The amount of dissolved oxygen in the molten steel 5 minutes before the end of the RH vacuum degassing treatment is set to within the range of 40 to 120 ppm. (v) Before the RH vacuum degassing treatment is completed, Al is added to the molten steel to perform deoxidation treatment, and the deoxidation treatment time by adding Al is limited to 5 minutes or less.

[0103] [Regarding condition (iii)] If the molten steel temperature during RH vacuum degassing is less than 1550°C, coarse, aggregated MnS-based inclusions will crystallize even if the oxygen content of the molten steel is 40 to 120 ppm. In this case, the aggregated MnS-based inclusions float to the surface and are absorbed into the slag, or the MnS-based inclusions remain in the steel in a coarse form, decreasing the number of MnS-based inclusions in the finished steel product. As a result, the surface number density (SN) of MnS-based inclusions with a circle equivalent diameter of 5.0 μm or more in the steel product is 20 pieces / mm 2 It will be less than.

[0104] [Regarding condition (iv)] If the amount of dissolved oxygen in the molten steel 5 minutes before the end of the RH vacuum degassing treatment is less than 40 ppm, a large amount of MnS is produced that does not use oxides as nuclei, and the amount of MnS composite oxide produced is reduced. Therefore, in the steel material, the ratio of the number of MnS composite oxides having a circle equivalent diameter of 1.0 μm or more to the total number of oxides (single oxides and MnS composite oxides) having a circle equivalent diameter of 1.0 μm or more (i.e., the MnS composite oxide number ratio RA OX ) will be less than 30%.

[0105] On the other hand, if the amount of dissolved oxygen in the molten steel 5 minutes before the end of the RH vacuum degassing process exceeds 120 ppm, coarse MnS-based inclusions are formed. In this case, coarse MnS-based inclusions are formed in the steel material, and the number of MnS-based inclusions themselves decreases. As a result, the surface number density (SN) of MnS-based inclusions with a circle equivalent diameter of 5.0 μm or more in the steel material is 20 pieces / mm 2In addition, the ratio of the total number of MnS single inclusions with a circle equivalent diameter of 1.0 μm or more and MnS composite inclusions with a circle equivalent diameter of 1.0 μm or more to the total number of inclusions with a circle equivalent diameter of 1.0 μm or more in the steel product (i.e., the MnS inclusion number ratio RA MnS ) is less than 70.0%.

[0106] [Regarding condition (v)] If the deoxidation treatment time by adding Al before the end of the RH vacuum degassing treatment exceeds 5 minutes, a large number of coarse single oxides are formed in the molten steel. In this case, the coarse single oxides do not function as nuclei for the formation of MnS-based inclusions in the casting process. As a result, MnS single inclusions that do not bond with the single oxides are formed, and the formation of MnS compound oxides is suppressed. As a result, in the product steel, the ratio of the number of MnS compound oxides with a circle equivalent diameter of 1.0 μm or more to the total number of oxides with a circle equivalent diameter of 1.0 μm or more (i.e., the MnS compound oxide number ratio RA OX ) will be less than 30%.

[0107] By adjusting the temperature of molten steel during the RH vacuum degassing treatment to 1550°C or higher, adjusting the amount of dissolved oxygen in the molten steel during the RH vacuum degassing treatment so that the amount of dissolved oxygen in the molten steel 5 minutes before the end of the RH vacuum degassing treatment is 40 to 120 ppm, and limiting the treatment time of the deoxidation treatment by adding Al before the end of the RH vacuum degassing treatment to 5 minutes or less, it is possible to suppress the formation of coarse MnS-based inclusions in the molten steel before the next casting process, and to form a large number of fine oxides that function as nuclei for the formation of MnS in the next casting process.

[0108] [Continuous casting process] In the continuous casting process, the molten steel after the refining process is used to produce blooms by a continuous casting method. In the continuous casting process, casting is performed under the following conditions. (vi) The casting speed from the start of continuous casting to the end of continuous casting is set to 0.6 to 1.0 m / min.

[0109] [Regarding condition (vi)] If the casting speed in the continuous casting process is less than 0.6 m / min, the casting speed is too slow. In this case, MnS-based inclusions are generated in the solidification stage, but they become coarse, resulting in a decrease in the number of MnS-based inclusions themselves. As a result, in the product steel material, the ratio of the total number of MnS single inclusions with an equivalent circle diameter of 1.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 1.0 μm or more to the total number of inclusions with an equivalent circle diameter of 1.0 μm or more (i.e., the MnS-based inclusion number ratio RA MnS ) is less than 70%.

[0110] On the other hand, if the casting speed in the continuous casting process exceeds 1.0 m / min, the casting speed is too fast and MnS-based inclusions are formed in the concentrated molten steel. In this case, MnS is not bonded to single oxides and is formed as MnS single inclusions. As a result, in the product steel, the ratio of the number of MnS complex oxides with a circle equivalent diameter of 1.0 μm or more to the total number of oxides with a circle equivalent diameter of 1.0 μm or more (i.e., the MnS complex oxide number ratio RA OX ) will be less than 30%.

[0111] By the above refining and casting steps, a bloom containing inclusions that satisfy the above (I) to (III) is produced.

[0112] [Hot processing process] In the hot working process, the bloom produced by the continuous casting process is subjected to hot working to produce a steel material. The shape of the steel material is a steel bar.

[0113] The hot working process includes a rough rolling process and a finish rolling process. In the rough rolling process, a billet is produced by hot working the material. For example, a blooming mill is used in the rough rolling process. Blooms are bloomed by the blooming mill to produce billets. If a continuous rolling mill is installed downstream of the blooming mill, the billet after blooming may be further hot rolled by the continuous rolling mill to produce a smaller billet. In the continuous rolling mill, a horizontal stand having a pair of horizontal rolls and a vertical stand having a pair of vertical rolls are alternately arranged in a row. Through the above steps, a billet is produced from the bloom in the rough rolling process. The heating temperature in the heating furnace in the rough rolling process is not particularly limited, but is, for example, 1100 to 1300°C.

[0114] In the finish rolling process, a billet is first heated using a heating furnace. The heated billet is hot-rolled using a continuous rolling mill to produce a steel bar. The heating temperature in the heating furnace in the finish rolling process is not particularly limited, but is, for example, 1000 to 1250°C. In addition, in the finish rolling, the steel temperature at the exit side of the rolling stand where the final reduction is performed is defined as the finishing temperature. At this time, the finishing temperature is, for example, 900 to 1150°C. The finishing temperature is measured by a thermometer installed at the exit side of the rolling stand where the final reduction is performed. The steel after the finish rolling is cooled at a cooling rate equal to or lower than the natural cooling rate to produce the steel of this embodiment.

[0115] In the above-mentioned manufacturing method, the hot working step includes a rough rolling step and a finish rolling step to manufacture the steel material. However, the finish rolling step in the hot rolling step may be omitted. In addition, the hot working step may be omitted from the above-mentioned manufacturing method. Even with these manufacturing methods, it is possible to manufacture the steel material of this embodiment, which has a chemical composition in which the contents of each element in the above-mentioned chemical composition are within the range of this embodiment, Fn1 and Fn2 are within the range of this embodiment, and which satisfies the above-mentioned (I) to (III).

[0116] [Manufacturing method of crankshaft] Next, an example of a method for manufacturing the crankshaft of this embodiment using the steel material of this embodiment will be described.

[0117] An example of a method for manufacturing a steel material according to this embodiment includes a hot forging step, a cutting step, and a nitriding step.

[0118] [Hot forging process] Hot forging is performed on the steel material of the present embodiment described above to manufacture an intermediate product having the shape of a crankshaft. The heating temperature of the steel material before hot forging is, for example, 1100 to 1350°C. The heating temperature here means the furnace temperature (°C) of the heating furnace. The holding time at the heating temperature is not particularly limited, but the steel material is held until its temperature becomes equivalent to the furnace temperature. The finishing temperature in hot forging is, for example, 1000 to 1300°C.

[0119] The intermediate product after hot forging is cooled by a known method, for example, by natural cooling. If necessary, the intermediate product after cooling is subjected to a blasting treatment such as shot blasting to remove oxide scale formed during hot forging.

[0120] [Cutting process] After the hot forging process, the intermediate product is cut to make it closer to the final product shape.

[0121] [Nitriding process] The intermediate product after cutting is subjected to a nitriding treatment. In this embodiment, a well-known nitriding treatment is adopted. The nitriding treatment is, for example, gas nitriding, salt bath nitriding, ion nitriding, etc. The atmosphere in the furnace during nitriding may be only NH3, or may be a mixture containing NH3, N2 and / or H2. Furthermore, carburizing gas may be added to these gases to perform the soft nitriding treatment. In other words, the nitriding treatment in this specification includes soft nitriding treatment.

[0122] When gas soft nitriding is performed, for example, an atmosphere of a 1:1 mixture of endothermic conversion gas (RX gas) and ammonia gas is used, the nitriding temperature is 500 to 650°C, and the holding time at the nitriding temperature is 0.5 to 8.0 hours. The intermediate product after the nitriding is quenched. The quenching method is water cooling or oil cooling. The nitriding conditions are not limited to the above, and may be appropriately adjusted so that the nitrided layer has the desired depth.

[0123] By the above nitriding process, a crankshaft having a nitrided layer formed on its surface is manufactured. EXAMPLES

[0124] The effects of the steel material and crankshaft of this embodiment will be described in more detail below using examples (first and second examples). The conditions in the following examples are one example of conditions adopted to confirm the feasibility and effects of the steel material and crankshaft of this embodiment. Therefore, the steel material and crankshaft of this embodiment are not limited to this one example of conditions.

[0125] [First Example] [Production of test materials] Molten steel having the chemical compositions shown in Tables 1 and 2 was produced in a 70 ton converter.

[0126] [Table 1]

[0127] [Table 2]

[0128] The "Other" column in Table 1 indicates the content of optional elements. For example, "0.20Cu" means that the Cu content was 0.20%. "-" means that the content of optional elements was below the detection limit and that optional elements were not included. After primary refining of the molten steel, secondary refining was performed. In the secondary refining, refining at the LF was performed first. The temperature of the molten steel during refining at the LF is shown in the "Molten steel temperature (℃)" column in the "LF" column in Table 3, and the oxygen content of the molten steel during refining at the LF is shown in the "Dissolved oxygen content (ppm)" column in the "LF" column in Table 3.

[0129] [Table 3]

[0130] After refining in the LF, RH vacuum degassing was performed. The temperature of molten steel during RH vacuum degassing is shown in the "Molten steel temperature (℃)" column of the "RH" column in Table 3. The amount of dissolved oxygen in the molten steel 5 minutes before the end of the RH vacuum degassing is shown in the "Dissolved oxygen amount (ppm)" column of the "RH" column in Table 3. The deoxidation time by adding Al before the end of the RH vacuum degassing is shown in the "Al deoxidation time (min)" column of the "RH" column in Table 3. In the "Molten steel temperature (℃)" column of the "LF" column, "X1-X2" means that the molten steel temperature during refining in the LF fluctuated within the range of X1 to X2℃. In the "Dissolved oxygen amount (ppm)" column of the "LF" column, "X3-X4" means that the oxygen content of the molten steel during refining in the LF fluctuated within the range of X3 to X4 ppm. In the "RH" column, in the "Molten steel temperature (℃)" column, "X5-X6" means that the molten steel temperature during the RH vacuum degassing process fluctuated within the range of X5 to X6°C. In the "RH" column, in the "Dissolved oxygen content (ppm)" column, "X7-X8" means that the dissolved oxygen content of the molten steel 5 minutes before the end of the RH vacuum degassing process fluctuated within the range of X7 to X8 ppm. In the "RH" column, in the "Al deoxidation treatment time (min)" column, "X9" means that the deoxidation treatment time by adding Al before the end of the RH vacuum degassing process was X9 minutes.

[0131] Blooms were produced by continuous casting using the molten steel after secondary refining. The casting speed from the start to the end of continuous casting is shown in the "Casting speed (mm / min)" column of the "Continuous casting" section in Table 3. In the "Casting speed (mm / min)" column of the "Continuous casting" section, "X10-X11" means that the casting speed from the start to the end of continuous casting varied within the range of X10 to X11 mm / min.

[0132] The produced blooms were subjected to a rough rolling process to produce billets having a rectangular cross section perpendicular to the longitudinal direction of 180 mm x 180 mm. The heating temperatures in the rough rolling processes were all within the range of 1200 to 1260°C. The produced billets were subjected to a finish rolling process and allowed to cool in the atmosphere to produce steel materials that were steel bars having a diameter of 80 mm. The heating temperatures in the finish rolling process were 1050 to 1200°C, and the finishing temperatures were 900 to 1150°C. Through the above manufacturing processes, the steel materials that would become the raw materials for crankshafts were produced.

[0133] The following evaluation tests were carried out on the steel materials with each test number.

[0134] [Evaluation test] [Inclusion measurement test] For each test number, the surface density SN and the ratio of MnS inclusions RA MnS , MnS complex oxide number ratio RA OX was calculated in the following way:

[0135] Samples were taken from the steel material of each test number. Specifically, as shown in Fig. 1, samples were taken from the R / 2 position (R is the radius of the steel material) in the radial direction from the central axis C1 of the steel material 1. The observation surface of the sample was L1 x L2, where L1 was 10 mm, L2 was 5 mm, and the sample thickness L3, which was perpendicular to the observation surface, was 5 mm. The normal N to the observation surface was perpendicular to the central axis C1 (i.e., the observation surface was parallel to the axial direction of the steel material), and the R / 2 position was approximately the center position of the observation surface.

[0136] The observation surface of the collected sample was polished to a mirror finish, and 50 random fields of view (field area per field: 125 μm × 75 μm) were observed at 2000x magnification using a scanning electron microscope (SEM).

[0137] In each field of view, inclusions were identified based on the contrast. Next, energy dispersive X-ray spectroscopy (EDX) was used to identify MnS inclusions, MnS composite inclusions, and MnS composite oxides from among the identified inclusions. Specifically, a beam was irradiated onto each inclusion in the field of view to detect characteristic X-rays and perform elemental analysis of the inclusions. Based on the results of the elemental analysis of each inclusion, the inclusions were identified as follows: (a) When the total content of Mn and S in an inclusion is 80.0% or more by mass, the inclusion is defined as a "single MnS inclusion." (b) When the total content of Mn and S in an inclusion is within the range of 15.0 to less than 80.0% by mass, the inclusion is defined as a "MnS composite inclusion." (c) If the total of the Al content, Ca content, and O content in an inclusion is 80.0% or more by mass, and the total of the Mn content and S content is less than 15.0% by mass, the inclusion is defined as a "single oxide." (d) In an inclusion, if the total of the Al content, Ca content, and O content is within the range of 15.0 to less than 80.0% by mass, and the total of the Mn content and S content is within the range of 15.0 to less than 80.0% by mass, the inclusion is defined as a "MnS composite oxide."

[0138] The inclusions to be identified were those with a circle equivalent diameter of 1.0 μm or more. The EDX beam diameter used to identify the inclusions was about 50 nm.

[0139] [Determination of surface density SN] Of the inclusions identified in the 50 visual fields, the total number of MnS single inclusions with an equivalent circle diameter of 5.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 5.0 μm or more was calculated. The surface density SN (numbers / mm 2 ) was sought.

[0140] [MnS-based inclusion number ratio RA MnS Decision Of the inclusions identified in the 50 visual fields, the total number of inclusions with an equivalent circle diameter of 1.0 μm or more was calculated. Furthermore, of the inclusions identified in the 50 visual fields, the total number of MnS single inclusions with an equivalent circle diameter of 1.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 1.0 μm or more was calculated. Based on the total number of inclusions with an equivalent circle diameter of 1.0 μm or more and the total number of MnS single inclusions with an equivalent circle diameter of 1.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 1.0 μm or more, the number ratio of MnS-based inclusions RA was calculated according to the following formula: MnS (%) was calculated. RA MnS = (Total number of MnS single inclusions with an equivalent circle diameter of 1.0 μm or more and MnS composite inclusions with an equivalent circle diameter of 1.0 μm or more) / (Total number of inclusions with an equivalent circle diameter of 1.0 μm or more) × 100

[0141] [MnS complex oxide number ratio RA OX Decision Of the inclusions identified in the 50 visual fields, the total number of oxides (single oxides and MnS composite oxides) with an equivalent circle diameter of 1.0 μm or more was calculated. Furthermore, of the inclusions identified in the 50 visual fields, the total number of MnS composite oxides with an equivalent circle diameter of 1.0 μm or more was calculated. Based on the total number of oxides with an equivalent circle diameter of 1.0 μm or more and the total number of MnS composite oxides with an equivalent circle diameter of 1.0 μm or more, the MnS composite oxide number ratio RA was calculated according to the following formula: OX (%) was calculated. RA OX = (total number of MnS composite oxides with a circle equivalent diameter of 1.0 μm or more) / (total number of oxides with a circle equivalent diameter of 1.0 μm or more) × 100

[0142] [Bending fatigue test] Hot forging and stretching was carried out on the steel material (steel bar with a diameter of 80 mm) of each test number, simulating the hot forging process in the manufacturing process of crankshafts. Specifically, the steel material was heated at 1200°C. The heated steel material was subjected to hot forging and stretching, and then allowed to cool to room temperature in the air to produce a forged and stretched material with a diameter of 50 mm. The finishing temperature in the hot forging and stretching was 1000 to 1050°C.

[0143] An Ono-type rotating bending fatigue test specimen (hereafter referred to as fatigue test specimen) shown in Figure 4 was taken from the R / 2 position of the forged and stretched material. The longitudinal direction of the fatigue test specimen was parallel to the longitudinal direction of the forged and stretched material. The central axis of the fatigue test specimen nearly coincided with the R / 2 position. The numbers marked with mm in Figure 4 indicate dimensions (unit: mm). In Figure 4, "φ" indicates diameter and "R" indicates radius of curvature.

[0144] The prepared fatigue test specimens were subjected to a soft nitriding treatment, which simulates the nitriding treatment in the manufacturing process of crankshafts. The treatment temperature in the soft nitriding treatment was set to 580-600°C, and the holding time at the treatment temperature was set to 1.5-2.0 hours. The atmospheric gas in the soft nitriding treatment was a well-known atmospheric gas (NH3+RX gas). The fatigue test specimens after the holding time were water-cooled to prepare fatigue test specimens simulating crankshafts.

[0145] The Ono-type rotating bending fatigue test was carried out using the fatigue test specimens. Specifically, the test was performed at room temperature in air at a rotation speed of 3000 rpm (50 Hz) and the test cutoff number was 1×10 7 The test was performed under three stress amplitude conditions of 600 MPa, 630 MPa, and 660 MPa, and the number of tests at each stress amplitude was N=2. Based on the results, the bending fatigue strength was evaluated as follows.

[0146] Rating A: No breakage both times at a stress amplitude of 660 MPa (durability) Rating B: No breakage both times at a stress amplitude of 630 MPa (durability), breakage at least once at a stress amplitude of 660 MPa Rating C: No breakage both times at a stress amplitude of 600 MPa (durability), breakage at least once at a stress amplitude of 630 MPa Grade D: Fracture occurred at least once at a stress amplitude of 600 MPa In the cases of evaluations A to C, it was determined that the rotating bending fatigue strength was excellent, and in the case of evaluation D, it was determined that the rotating bending fatigue strength was low.

[0147] [Bending straightening evaluation test] Hot forging and stretching was carried out on the steel material (steel bar with a diameter of 80 mm) of each test number, simulating the hot forging process in the manufacturing process of crankshafts. Specifically, the steel material was heated at 1200°C. The heated steel material was subjected to hot forging and stretching, and then allowed to cool to room temperature in the air to produce a forged and stretched material with a diameter of 50 mm. The finishing temperature in the hot forging and stretching was 1000 to 1050°C.

[0148] A four-point bending test specimen as shown in FIG. 5 was taken from the R / 2 position of the forged and stretched material. FIG. 5 shows a front view 210, a side view 220, and a plan view 230 of the four-point bending test specimen. The numbers marked with "mm" in the figures indicate dimensions. The dimensions marked with "R" in the figures indicate the radius of curvature. A semicircular notch (radius of curvature at the notch bottom 3 mm, depth 2 mm) extending perpendicular to the longitudinal direction was provided at the longitudinal center of the four-point bending test specimen.

[0149] The prepared four-point bending test specimen was subjected to a soft nitriding treatment, which simulates the nitriding treatment in the manufacturing process of crankshafts. The treatment temperature in the soft nitriding treatment was set to 580-600°C, and the holding time at the treatment temperature was set to 1.5-2.0 hours. The atmospheric gas in the soft nitriding treatment was a well-known atmospheric gas (NH3+RX gas). The fatigue test specimen after the holding time was water-cooled to prepare a four-point bending test specimen simulating a crankshaft.

[0150] A bending straightening test was carried out on the four-point bending test pieces thus prepared. First, a strain gauge with a gauge length of 2 mm was attached (glued) to the bottom of the notch of the notch of the four-point bending test piece. Then, a four-point bending test was carried out in which a tensile strain was applied to the bottom of the notch by the four-point bending method until the strain gauge broke. In the four-point bending test, four-point bending was carried out with a distance between the inner supports of 30 mm and a distance between the outer supports of 80 mm. The strain rate during four-point bending was 2 mm / min. The maximum strain amount (με) when the strain gauge broke was obtained. The four-point bending test was carried out 10 times for each test number, and the average of the maximum strain amounts obtained in the ten tests was taken as the bending straightening strain amount. Based on the obtained bending straightening strain amount, the bending straightening property was evaluated as follows. Evaluation A: The bending straightening strain amount is 40000 με or more. Evaluation B: The bending straightening strain amount is less than 30,000 to 40,000 με. Evaluation C: The bending straightening strain amount is less than 20,000 to 30,000 με. Evaluation D: The amount of bending straightening strain is less than 20000 με. In the cases of evaluations A to C, it was determined that the bending straightening ability was excellent, and in the case of evaluation D, it was determined that the bending straightening ability was poor.

[0151] [Machinability evaluation test] Hot forging and stretching was carried out on the steel material (steel bar with a diameter of 80 mm) of each test number, simulating the hot forging process in the manufacturing process of crankshafts. Specifically, the steel material was heated at 1200°C. The heated steel material was subjected to hot forging and stretching, and then allowed to cool to room temperature in the air to produce a forged and stretched material with a diameter of 50 mm. The finishing temperature in the hot forging and stretching was 1000 to 1050°C. The forged and stretched material was cut in a direction perpendicular to the longitudinal direction to obtain a sample with a diameter of 50 mm and a length of 200 mm.

[0152] A gun drill was used to drill holes at the R / 2 position on the surface (cut surface) perpendicular to the longitudinal direction of the sample, and the machinability was evaluated. Specifically, a standard gun drill (manufactured by Tungaloy Corporation, without a breaker) with a diameter of 9.5 mm was used to drill holes parallel to the axial direction at the R / 2 position. The cutting speed during drilling was 107 mm / min (drill rotation speed 3600 rpm), the feed rate was 0.023 mm / rev, and the drilling distance was 90 mm / hole. After drilling 200 holes under the above conditions, the wear amount of the flank of the gun drill was measured. Depending on the obtained wear amount, the machinability was evaluated as follows. Grade A: Wear amount is less than 30 μm Grade B: Wear amount is less than 30 to 40 μm Grade C: Wear amount is less than 40 to 50 μm Grade D: Wear amount is 50 μm or more In the cases of ratings A to C, the machinability was judged to be excellent, and in the case of rating D, the machinability was judged to be poor.

[0153] [Wear resistance evaluation test] A 10mm x 15mm x 6.35mm block was taken from the R / 2 position of the 50mm diameter forged and stretched material produced for the machinability evaluation test. The 15mm x 6.35mm test surface was parallel to the central axis of the forged and stretched material.

[0154] The block material was subjected to soft nitriding treatment, which simulates the nitriding treatment in the manufacturing process of crankshafts. The treatment temperature in the soft nitriding treatment was set to 580-600°C, and the holding time at the treatment temperature was set to 1.5-2.0 hours. The atmospheric gas in the soft nitriding treatment was a well-known atmospheric gas (NH3 + RX gas). After the holding time had elapsed, the block material was water-cooled to prepare a block test piece simulating a crankshaft.

[0155] The test surface (10 mm × 6.35 mm) of the block test piece was subjected to lapping processing to obtain an arithmetic mean roughness Ra of the test surface of 0.2. The arithmetic mean roughness Ra was measured in accordance with JIS B 0601 (2013) and the reference length was set to 5 mm.

[0156] A block-on-ring wear test shown in FIG. 6 was carried out using the sample material. Referring to FIG. 6, a block-on-ring wear tester 100 was equipped with a bath 101 containing lubricating oil 102, and a ring test piece 103. A commercially available engine oil with a viscosity of 0W-20 was used as the lubricating oil 102. The material of the ring test piece 103 was an Al alloy, which is a common bearing metal material. The Al alloy contained, by mass, 12% Sn and 3% Si, with the remainder being Al. The outer diameter D of the ring test piece 103 was 35 mm, and the width W of the ring test piece 103 was 8.7 mm.

[0157] As shown in FIG. 6, the lower part of the ring test piece 103 was immersed in the lubricating oil 102 in the bath 101. Then, the block test piece 50 was placed above the ring test piece 103. At this time, the block test piece 50 was placed so that the test surface 51 of the block test piece 50 faced the ring test piece 103. The ring test piece 103 was rotated while the block test piece 50 was pressed against the outer peripheral surface of the ring test piece 103 from above to below with a load P of 100 N, and a wear test was performed. At this time, the rotation speed of the ring test piece 103 was set to 700 rpm, and the sliding speed was set to 1.28 m / sec. The test was interrupted every 60 minutes after the start of the test, and the lubricating oil was wiped off from the contact portion 52 of the test surface 51 of the block test piece 50 with the outer peripheral surface of the ring test piece 103, and then the test was resumed. This action was repeated until the total sliding time (test time) reached 100 hours. The test was terminated when the sliding time (test time) reached 100 hours.

[0158] After the test, the contact portion 52 of the test surface 51 of the block test piece 50 was observed at 1000x magnification in 5 arbitrary fields (each field 250μm×150μm) using an SEM to check for peeling of the compound layer and for microcracks in the compound layer. Based on the results of the examination, the abrasion resistance was evaluated as follows. Evaluation A: No peeling, no microcracks Evaluation B: No peeling, fine cracks Rating D: Peeling The samples with ratings of A and B were judged to have excellent abrasion resistance, while the sample with rating of D was judged to have poor abrasion resistance.

[0159] [Test Results] Tables 4 and 5 show the test results.

[0160] [Table 4]

[0161] [Table 5]

[0162] Referring to Tables 4 and 5, the contents of each element in the chemical composition of test numbers 1 to 63 were appropriate, Fn1 was 1.00 to 2.05, and Fn2 was 0.42 to 0.60. Furthermore, the manufacturing conditions were also appropriate. Therefore, the surface density SN was 20 pieces / mm 2 The ratio of the number of MnS-based inclusions RA MnS is 70% or more, and the number ratio of MnS complex oxides RA OX The ratio of the rotating bending fatigue strength to the bending strength was 30% or more. Therefore, excellent rotating bending fatigue strength, excellent bending straightening property, excellent machinability, and excellent wear resistance were obtained.

[0163] On the other hand, the C content of test number 64 was too high, so the bending straightening strain was less than 20000 με, and the bending straightening property was low.

[0164] The carbon content of test number 65 was too low. Therefore, in the Ono-type rotating bending fatigue test, the carbon content was 1×10 at a stress amplitude of 600 MPa. 7 The specimen broke before reaching the bending cycle and had low bending fatigue strength.

[0165] The Si content of test number 66 was too high, so the bending straightening strain was less than 20,000 με, and bending straightening property was poor.

[0166] The Si content of test number 67 was too low. Therefore, in the Ono-type rotating bending fatigue test, the Si content was 1×10 7 The specimen broke before reaching the bending cycle and had low bending fatigue strength.

[0167] The Mn content of test number 68 was too high, so the bending straightening strain was less than 20000με, and the bending straightening property was low.

[0168] The Mn content of test number 69 was too low. Therefore, in the Ono-type rotating bending fatigue test, the fatigue strength was 1×10 at a stress amplitude of 600 MPa. 7 The specimen broke before reaching the bending cycle and had low bending fatigue strength.

[0169] The P content of test number 70 was too high. Therefore, in the Ono-type rotating bending fatigue test, the P content was 1×10 at a stress amplitude of 600 MPa. 7 The specimen broke before reaching the bending cycle and had low bending fatigue strength.

[0170] The S content of test number 71 was too low. As a result, the wear amount on the flank of the gun drill exceeded 50 μm in the machinability evaluation test, and the machinability was poor.

[0171] The Cr content of test number 72 was too high, so the bending straightening strain was less than 20000με, and the bending straightening property was poor.

[0172] The Ti content of test number 73 was too high. Therefore, in the Ono-type rotating bending fatigue test, the Ti content was 1×10 at a stress amplitude of 600 MPa. 7 The specimen broke before reaching the bending cycle and had low bending fatigue strength.

[0173] The Al content of test number 74 was too high, so the bending straightening strain was less than 20000με, and bending straightening property was low.

[0174] The N content of test number 75 was too low. Therefore, in the Ono-type rotating bending fatigue test, the fatigue strength was 1×10 at a stress amplitude of 600 MPa. 7 The specimen broke before reaching the bending cycle and had low bending fatigue strength.

[0175] The O content of test number 76 was too high. Therefore, in the Ono-type rotating bending fatigue test, the O content was 1×10 at a stress amplitude of 600 MPa. 7 The specimen broke before reaching the bending fatigue strength, indicating that the bending fatigue strength was low. In addition, peeling of the compound layer was observed on the test surface of the block specimen after the block-on-ring wear test, indicating that the wear resistance was low.

[0176] In test number 77, although the contents of each element were within the range of the present embodiment, Fn1 defined by formula (1) exceeded the upper limit, and therefore the straightening strain was less than 20000 με, and the straightening property was poor.

[0177] In test number 78, the contents of each element were within the range of the present embodiment, but Fn1 defined by formula (1) was below the lower limit. Therefore, in the Ono-type rotating bending fatigue test, 7 The specimen broke before reaching the bending cycle and had low bending fatigue strength.

[0178] In test number 79, although the contents of each element were within the range of this embodiment, Fn2 defined by formula (2) exceeded the upper limit, and therefore the wear amount on the flank of the gun drill was 50 μm or more in the machinability evaluation test, and the machinability was poor.

[0179] In test number 80, the contents of each element were within the range of the present embodiment, but Fn2 defined by formula (2) was below the lower limit. Therefore, in the Ono-type rotating bending fatigue test, 7 The specimen broke before reaching the bending cycle and had low bending fatigue strength.

[0180] In test number 81, the contents of each element in the chemical composition were within the range of this embodiment, and Fn1 and Fn2 were also within the range of this embodiment, but the amount of dissolved oxygen during refining in the LF exceeded 40 ppm. Therefore, the surface density SN was 20 particles / mm 2 As a result, in the machinability evaluation test, the wear amount on the flank of the gun drill was 50 μm or more, and the machinability was low.

[0181] In test number 82, the contents of each element in the chemical composition were within the range of this embodiment, and Fn1 and Fn2 were also within the range of this embodiment, but the casting speed in the continuous casting process was less than 0.6 m / min. MnS As a result, peeling of the compound layer was observed on the test surface of the block test piece after the block-on-ring wear test, and the wear resistance was low.

[0182] In test number 83, the contents of each element in the chemical composition were within the range of this embodiment, and Fn1 and Fn2 were also within the range of this embodiment, but the amount of dissolved oxygen in the molten steel 5 minutes before the end of the RH vacuum degassing treatment was less than 40 ppm. OX As a result, peeling of the compound layer was observed on the test surface of the block test piece after the block-on-ring wear test, and the wear resistance was low.

[0183] [Second Example] [Production of test materials] Molten steel having the chemical composition shown in Table 6 was produced in a 70 ton converter.

[0184] [Table 6]

[0185] Secondary refining was carried out on the molten steel. In the secondary refining, refining was first carried out in the LF. The oxygen content of the molten steel during refining in the LF is shown in the "Dissolved oxygen content (ppm)" column of the "LF" column in Table 7, and the temperature of the molten steel during refining in the LF is shown in the "Molten steel temperature (℃)" column of the "LF" column in Table 7.

[0186] [Table 7]

[0187] After refining in the LF, RH vacuum degassing was performed. The temperature of molten steel during RH vacuum degassing is shown in the "Molten steel temperature (℃)" column of the "RH" column in Table 7. The amount of dissolved oxygen in the molten steel 5 minutes before the end of the RH vacuum degassing is shown in the "Dissolved oxygen amount (ppm)" column of the "RH" column in Table 2. The deoxidation time by adding Al before the end of the RH vacuum degassing is shown in the "Al deoxidation time (min)" column of the "RH" column in Table 7. In the "Molten steel temperature (℃)" column of the "LF" column, "X1-X2" means that the molten steel temperature during refining in the LF fluctuated within the range of X1 to X2℃. In the "Dissolved oxygen amount (ppm)" column of the "LF" column, "X3-X4" means that the oxygen content of the molten steel during refining in the LF fluctuated within the range of X3 to X4 ppm. In the "RH" column, in the "Molten steel temperature (℃)" column, "X5-X6" means that the molten steel temperature during the RH vacuum degassing process fluctuated within the range of X5 to X6°C. In the "RH" column, in the "Dissolved oxygen content (ppm)" column, "X7-X8" means that the dissolved oxygen content of the molten steel 5 minutes before the end of the RH vacuum degassing process fluctuated within the range of X7 to X8 ppm. In the "RH" column, in the "Al deoxidation treatment time (min)" column, "X9" means that the deoxidation treatment time by adding Al before the end of the RH vacuum degassing process was X9 minutes.

[0188] Blooms were produced by continuous casting using the molten steel after secondary refining. The casting speed from the start to the end of continuous casting is shown in the "Casting speed (mm / min)" column of the "Continuous casting" section of Table 7. In the "Casting speed (mm / min)" column of the "Continuous casting" section, "X10-X11" means that the casting speed from the start to the end of continuous casting varied within the range of X10 to X11 mm / min.

[0189] The produced blooms were subjected to a rough rolling process to produce billets having a rectangular shape with a cross section perpendicular to the longitudinal direction of 180 mm × 180 mm. The heating temperature in the rough rolling process was in the range of 1200 to 1260°C in each case.

[0190] The produced billets were subjected to finish rolling and allowed to cool in the air to produce steel bars having a diameter of 80 mm. The following evaluation tests were carried out on the steel bars having each test number.

[0191] [Evaluation test] [Inclusion measurement test] For each test number, the surface density SN and the ratio of MnS inclusions RA MnS , MnS complex oxide number ratio RA OX was obtained by the same method as in the first embodiment.

[0192] [Machinability evaluation test] For each test number, the machinability evaluation test was carried out in the same manner as in the first example, and the machinability was evaluated according to the same criteria as in the first example.

[0193] [Wear resistance evaluation test] For each test number, the abrasion resistance evaluation test was carried out in the same manner as in the first embodiment, and the abrasion resistance was evaluated according to the same criteria as in the abrasion resistance evaluation test in the first embodiment.

[0194] [Test Results] The test results are shown in Table 7. Referring to Table 7, the content of each element in the chemical composition of test numbers 84 to 90 was appropriate, Fn1 was 1.00 to 2.05, and Fn2 was 0.42 to 0.60. Furthermore, the manufacturing conditions were also appropriate. Therefore, the surface density SN was 20 pieces / mm 2 The ratio of the number of MnS-based inclusions RA MnS is 70.0% or more, and the number ratio of MnS complex oxides RA OX The ratio of the surface roughness to the surface roughness was 30.0% or more. Therefore, excellent rotating bending fatigue strength, excellent bending straightening property, excellent machinability, and excellent wear resistance were obtained.

[0195] On the other hand, in test number 91, the contents of each element in the chemical composition were within the range of this embodiment, and Fn1 and Fn2 were also within the range of this embodiment, but the molten steel temperature during refining in the LF was less than 1550°C. Therefore, the surface number density SN was 20 / mm 2 As a result, in the machinability evaluation test, the wear amount on the flank of the gun drill was 50 μm or more, and the machinability was low.

[0196] In test number 92, the contents of each element in the chemical composition were within the range of this embodiment, and Fn1 and Fn2 were also within the range of this embodiment, but the amount of dissolved oxygen during refining in the LF exceeded 40 ppm. Therefore, the surface number density SN was 20 pieces / mm 2 As a result, in the machinability evaluation test, the wear amount on the flank of the gun drill was 50 μm or more, and the machinability was low.

[0197] On the other hand, in test number 93, the contents of each element in the chemical composition were within the range of this embodiment, and Fn1 and Fn2 were also within the range of this embodiment, but the molten steel temperature during the RH vacuum degassing treatment was less than 1550°C. Therefore, the surface density SN was 20 / mm 2 As a result, in the machinability evaluation test, the wear amount on the flank of the gun drill was 50 μm or more, and the machinability was low.

[0198] In test number 94, the contents of each element in the chemical composition were within the range of this embodiment, and Fn1 and Fn2 were also within the range of this embodiment, but the amount of dissolved oxygen in the molten steel 5 minutes before the end of the RH vacuum degassing treatment exceeded 120 ppm. 2 Furthermore, the ratio of the number of MnS-based inclusions, RA MnS The wear resistance of the block specimen was less than 70%. As a result, peeling of the compound layer was observed on the test surface of the block specimen after the block-on-ring wear test, indicating low wear resistance. Furthermore, in the machinability evaluation test, the wear amount on the flank of the gun drill was 50 μm or more, indicating low machinability.

[0199] In test number 95, the contents of each element in the chemical composition were within the range of this embodiment, and Fn1 and Fn2 were also within the range of this embodiment, but the amount of dissolved oxygen in the molten steel 5 minutes before the end of the RH vacuum degassing treatment was less than 40 ppm. OX As a result, peeling of the compound layer was observed on the test surface of the block test piece after the block-on-ring wear test, and the wear resistance was low.

[0200] In test number 96, the contents of each element in the chemical composition were within the range of this embodiment, and Fn1 and Fn2 were also within the range of this embodiment, but the deoxidation treatment time by adding Al before the end of the RH vacuum degassing treatment exceeded 5 minutes. OX As a result, peeling of the compound layer was observed on the test surface of the block test piece after the block-on-ring wear test, and the wear resistance was low.

[0201] In test number 97, the contents of each element in the chemical composition were within the range of this embodiment, and Fn1 and Fn2 were also within the range of this embodiment, but the casting speed in the continuous casting process exceeded 1.0 m / min. Therefore, the number ratio RA of the MnS complex oxide OX As a result, peeling of the compound layer was observed on the test surface of the block test piece after the block-on-ring wear test, and the wear resistance was low.

[0202] In test number 98, the contents of each element in the chemical composition were within the range of this embodiment, and Fn1 and Fn2 were also within the range of this embodiment, but the casting speed in the continuous casting process was less than 0.6 m / min. MnS As a result, peeling of the compound layer was observed on the test surface of the block test piece after the block-on-ring wear test, and the wear resistance was low.

[0203] The above describes the embodiments of the present invention. However, the above-described embodiments are merely examples for carrying out the present invention. Therefore, the present invention is not limited to the above-described embodiments, and the above-described embodiments can be appropriately modified and carried out without departing from the spirit of the present invention. [Explanation of symbols]

[0204] 1 Steel material 10. Crankshaft 11 Pin section 12 Journal Section 13 Arm section 20 Nitrided layer 23 Core

Claims

1. A steel material, In mass percent, C: 0.25% to 0.35%, Si: 0.05-0.35%, Mn: 0.85 to 1.20%, P: 0.080% or less, S: 0.030-0.100%, Cr: 0.10% or less, Ti: 0.050% or less, Al: 0.050% or less, N: 0.005 to 0.024%, and O: 0.0100% or less; The balance is Fe and impurities, Fn1 defined by formula (1) is 1.00 to 2.05, Fn2 defined by formula (2) is 0.42 to 0.60, Among the inclusions in the steel material, An inclusion having a total Mn content and S content of 80.0% or more by mass% is defined as a MnS inclusion alone. An inclusion having a total Mn content and S content of 15.0 to less than 80.0% by mass is defined as an MnS complex inclusion, An inclusion having an Al content, a Ca content, and an O content of 80.0% or more by mass and an Mn content and an S content of less than 15.0% by mass is defined as a single oxide. When the inclusions having an Al content, Ca content and O content in total of 15.0 to less than 80.0% by mass and an Mn content and S content in total of 15.0 to less than 80.0% by mass are defined as MnS composite oxides, In the steel material, The total surface density of the MnS single inclusions having an equivalent circle diameter of 5.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 5.0 μm or more is 20 pieces / mm 2 That's all. a ratio of the total number of the MnS single inclusions having an equivalent circle diameter of 1.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 1.0 μm or more to the total number of inclusions having an equivalent circle diameter of 1.0 μm or more is 70% or more; a ratio of the number of the MnS composite oxide having an equivalent circle diameter of 1.0 μm or more to the total number of the single oxide having an equivalent circle diameter of 1.0 μm or more and the MnS composite oxide having an equivalent circle diameter of 1.0 μm or more is 30% or more; Steel material. Fn1=Mn+7.24Cr+6.53Al...(1) Fn2=C+0.10Si+0.19Mn+0.23Cr-0.34S...(2) Here, the content of each element in formula (1) and formula (2) is substituted in mass % for each element symbol corresponding to the element.

2. The steel material according to claim 1, Instead of a part of the Fe, Cu: 0.20% or less, Ni: 0.20% or less, Mo: 0.10% or less, Nb: 0.050% or less, Ca: 0.0100% or less, Bi: 0.30% or less, Te: 0.0100% or less, Zr: 0.0100% or less, and Pb: 0.09% or less, Contains one or more elements selected from the group consisting of Steel material.

3. A pin portion and The journal section and an arm portion disposed between the pin portion and the journal portion, At least the pin portion and the journal portion are A nitride layer formed on the surface; A core portion located inside the nitride layer, The core portion comprises, in mass%, C: 0.25% to 0.35%, Si: 0.05-0.35%, Mn: 0.85 to 1.20%, P: 0.080% or less, S: 0.030-0.100%, Cr: 0.10% or less, Ti: 0.050% or less, Al: 0.050% or less, N: 0.005 to 0.024%, and O: 0.0100% or less; The balance is Fe and impurities, Fn1 defined by formula (1) is 1.00 to 2.05, Fn2 defined by formula (2) is 0.42 to 0.60, Among the inclusions in the core portion, An inclusion having a total Mn content and S content of 80.0% or more by mass% is defined as a MnS inclusion alone. An inclusion having a total Mn content and S content of 15.0 to less than 80.0% by mass is defined as an MnS complex inclusion, An inclusion having an Al content, a Ca content, and an O content of 80.0% or more by mass and an Mn content and an S content of less than 15.0% by mass is defined as a single oxide. When the inclusions having an Al content, Ca content and O content in total of 15.0 to less than 80.0% by mass and an Mn content and S content in total of 15.0 to less than 80.0% by mass are defined as MnS composite oxides, In the core portion, The total surface density of the MnS single inclusions having an equivalent circle diameter of 5.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 5.0 μm or more is 20 pieces / mm 2 That's all. a ratio of the total number of the MnS single inclusions having an equivalent circle diameter of 1.0 μm or more and the MnS composite inclusions having an equivalent circle diameter of 1.0 μm or more to the total number of inclusions having an equivalent circle diameter of 1.0 μm or more is 70% or more; a ratio of the number of the MnS composite oxide having an equivalent circle diameter of 1.0 μm or more to the total number of the single oxide having an equivalent circle diameter of 1.0 μm or more and the MnS composite oxide having an equivalent circle diameter of 1.0 μm or more is 30% or more; Crankshaft. Fn1=Mn+7.24Cr+6.53Al...(1) Fn2=C+0.10Si+0.19Mn+0.23Cr-0.34S...(2) Here, the content of each element in formula (1) and formula (2) is substituted in mass % for each element symbol corresponding to the element.

4. 4. The crankshaft according to claim 3, The core portion further contains, instead of a part of the Fe, Cu: 0.20% or less, Ni: 0.20% or less, Mo: 0.10% or less, Nb: 0.050% or less, Ca: 0.0100% or less, Bi: 0.30% or less, Te: 0.0100% or less, Zr: 0.0100% or less, and Pb: 0.09% or less, Contains one or more elements selected from the group consisting of Crankshaft.

Citation Information

Patent Citations

  • Soft-nitrided non-heat-treated steel member

    JP2007197812A

  • Steel product

    JP2013007077A

  • Hot rolled bar wire rod

    JP2017115190A

  • Steel material, crank shaft and automobile component

    JP2017186658A

  • Non-heat treated steel for soft nitriding

    WO2005021816A1